Method for producing positive electrode active material particles

JP2026165117APending Publication Date: 2026-10-13SEMICON ENERGY LAB CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
JP2026053528
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2025-03-28
Filing Date
2026-03-27
Publication Date
2026-10-13

AI Technical Summary

Benefits of technology

【0016】 本発明の一態様により、充放電容量の大きなリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、粒径の小さなリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、初回の充電容量に対して初回の放電容量の低下が抑制されたリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、レート特性の良好なリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、充放電サイクルにおける電圧または放電容量の低下が抑制されたリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、充電時の結晶構造変化が抑制されたリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、酸素の離脱が抑制されたリチウム過剰系正極活物質粒子または複合酸化物を提供することができる。または、充放電容量、安全性又は信頼性の高い二次電池を提供することができる。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2026165117000001_ABST
    Figure 2026165117000001_ABST
Patent Text Reader

Abstract

This invention provides a method for producing lithium-rich cathode active material particles with high charge / discharge capacity and a stabilized crystal structure. [Solution] A method for producing positive electrode active material particles, comprising the steps of: mixing a lithium source and an M source (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti, and Ru) to produce a first mixture; heating the first mixture at 850°C or higher and less than 950°C to synthesize a first composite oxide; mixing the first composite oxide and an additive element source to produce a second mixture; and heating the second mixture at 850°C or higher and less than 950°C, wherein the additive element source is a fluorine source and a magnesium source.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical Field]

[0001] One aspect of the present invention relates to a product, a method, or a method of manufacture; or to a process, a machine, a manufacture, or a composition of matter. One aspect of the present invention relates to positive electrode active material particles, energy storage devices including secondary batteries, semiconductor devices, display devices, light-emitting devices, lighting devices, electronic devices, or methods for manufacturing the same.

[0002] In this specification, "electronic equipment" refers to all devices that have an energy storage device, and all electro-optical devices with an energy storage device, information terminal devices with an energy storage device, etc., are considered electronic equipment. [Background technology]

[0003] In recent years, there has been a great deal of activity in the development of lithium-ion secondary batteries, lithium-ion capacitors, air batteries, and various energy storage devices. In particular, lithium-ion secondary batteries, which offer high output and high energy density, are seeing rapidly expanding demand in conjunction with the development of the semiconductor industry. They are used in mobile information terminals such as mobile phones, smartphones, and notebook computers, portable music players, digital cameras, medical devices, and next-generation clean energy vehicles such as hybrid vehicles (HV), electric vehicles (EV), and plug-in hybrid vehicles (PHV), and have become indispensable to modern society as a source of rechargeable energy.

[0004] In lithium-ion secondary batteries, lithium cobalt oxide (LiCoO2) and lithium nickel cobalt manganese oxide (LiNi), which have a layered rock salt-type crystalline structure, are used as high-capacity positive electrode active materials. a Co b Mn c O2 (a+b+c=1), etc., have been put into practical use.

[0005] However, research and development are underway to achieve even higher capacity. Among these, cathode active materials known as lithium-rich or lithium-excessive systems are attracting attention because they can store far more lithium ions than current lithium cobalt oxide, lithium nickel cobalt manganese oxide, etc. (Non-Patent Documents 1 to 5). [Prior art documents] [Non-patent literature]

[0006] [Non-Patent Document 1] Reversible Oxygen Participation to the Redox Processes Revealed for Li1.20Mn0.54Co0.13Ni0.13O2. Hideyuki Koga et al., Journal of The Electrochemical Society, 160 (6) A786-A792 (2013) [Non-Patent Document 2] Functioning Mechanism of AlF3 Coating on the Li- and Mn-Rich Cathode Materials. Jianming Zheng et al., Chemistry of Materials, 26, 6320-6327 (2014) [Non-Patent Document 3] Lithium- and Manganese-Rich Oxide Cathode Materials for High-Energy Lithium Ion Batteries. Jun Wang et al., Advanced Energy Materials, 6, 1600906 (2016) [Non-Patent Document 4] Challenges and Recent Advances in High Capacity Li-Rich Cathode Materials for High Energy Density Lithium-Ion Batteries. Wei He et al., Advanced materials, 33, 2005937 (2021) [Non-Patent Document 5] In situ formed partially disordered phases as earth-abundant Mn-rich cathode materials. Zijian Cai et al., Nature Energy (2023). https: / / doi.org / 10.1038 / s41560-023-01375-9 [Overview of the project] [Problems that the invention aims to solve]

[0007] Lithium-rich cathode active materials offer numerous advantages. For example, they can increase the discharge capacity per unit weight of the cathode active material to over 250 mAh / g, and even over 300 mAh / g. Simultaneously, they can increase the energy density per unit weight to, for example, over 1000 Wh / kg. Furthermore, instead of cobalt, which presents cost and other problems, manganese, which is more inexpensive and abundant, can be used as the main transition metal.

[0008] On the other hand, lithium-rich cathode active materials have several drawbacks, including a large decrease in the initial discharge capacity relative to the initial charge capacity, poor rate characteristics, and a significant decrease in voltage and / or discharge capacity during charge-discharge cycle tests. This is thought to be because, in lithium-rich cathode active material particles, changes in the crystal structure and / or oxygen desorption occur when lithium is desorbed.

[0009] Furthermore, lithium-rich cathode active materials tend to have increased internal resistance and reduced charge / discharge capacity when their particle size increases during manufacturing processes such as heating.

[0010] Therefore, one aspect of the present invention aims to provide lithium-rich cathode active material particles or composite oxides with a large charge / discharge capacity. Alternatively, it aims to provide lithium-rich cathode active material particles or composite oxides in which the increase in particle size is suppressed. Alternatively, it aims to provide lithium-rich cathode active material particles or composite oxides in which the decrease in the initial discharge capacity relative to the initial charge capacity is suppressed. Alternatively, it aims to provide lithium-rich cathode active material particles or composite oxides with good rate characteristics. Alternatively, it aims to provide lithium-rich cathode active material particles or composite oxides in which the decrease in voltage or discharge capacity during the charge / discharge cycle is suppressed. Alternatively, it aims to provide lithium-rich cathode active material particles or composite oxides in which the change in crystal structure during charging is suppressed. Alternatively, it aims to provide lithium-rich cathode active material particles or composite oxides in which the departure of oxygen is suppressed. Alternatively, it aims to provide a secondary battery with high charge / discharge capacity, safety, or reliability.

[0011] Furthermore, one aspect of the present invention aims to provide novel positive electrode active material particles, composite oxides, energy storage devices, or methods for producing them.

[0012] Furthermore, the description of these problems does not preclude the existence of other problems. Moreover, one aspect of the present invention does not need to solve all of these problems. It is possible to extract other problems from the description in the specification, drawings, and claims. [Means for solving the problem]

[0013] To solve the above problems, in one aspect of the present invention, positive electrode active material particles are provided with a core-shell structure, and the shell is configured to contain a large amount of additive elements, including magnesium. Furthermore, a fluoride salt that functions as a flux is used to effectively dope the shell with additive elements.

[0014] One aspect of the present invention is a method for producing positive electrode active material particles, comprising the steps of: mixing a lithium source and an M source (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti, and Ru) to produce a first mixture; heating the first mixture at 850°C or higher and less than 950°C to synthesize a first composite oxide; mixing the first composite oxide and an additive element source to produce a second mixture; and heating the second mixture at 850°C or higher and less than 950°C, wherein the additive element source is a fluorine source and a magnesium source.

[0015] Furthermore, in the above, it is preferable that the fluorine source is lithium fluoride and the magnesium source is magnesium fluoride. [Effects of the Invention]

[0016] According to one aspect of the present invention, lithium-rich cathode active material particles or composite oxides with high charge / discharge capacity can be provided. Alternatively, lithium-rich cathode active material particles or composite oxides with small particle size can be provided. Alternatively, lithium-rich cathode active material particles or composite oxides in which the decrease in initial discharge capacity relative to the initial charge capacity is suppressed can be provided. Alternatively, lithium-rich cathode active material particles or composite oxides with good rate characteristics can be provided. Alternatively, lithium-rich cathode active material particles or composite oxides in which the decrease in voltage or discharge capacity during charge / discharge cycles is suppressed can be provided. Alternatively, lithium-rich cathode active material particles or composite oxides in which changes in crystal structure during charging are suppressed can be provided. Alternatively, lithium-rich cathode active material particles or composite oxides in which oxygen desorption is suppressed can be provided. Alternatively, a secondary battery with high charge / discharge capacity, safety, or reliability can be provided.

[0017] Furthermore, according to one aspect of the present invention, novel positive electrode active material particles, composite oxides, energy storage devices, or methods for producing them can be provided.

[0018] Furthermore, the description of these effects does not preclude the existence of other effects. Moreover, one aspect of the present invention does not necessarily have to possess all of these effects. Other effects will become clear from the description in the specification, drawings, and claims, and it is possible to extract other effects from the description in the specification, drawings, and claims. [Brief explanation of the drawing]

[0019] [Figure 1] Figure 1 is a schematic cross-sectional view of positive electrode active material particles according to one embodiment of the present invention. [Figure 2] Figures 2(A) to 2(C) illustrate the crystal structure of positive electrode active material particles according to one embodiment of the present invention. [Figure 3] Figures 3(A) and 3(B) illustrate an example of a method for producing positive electrode active material particles according to one embodiment of the present invention. [Figure 4] Figure 4 illustrates an example of a method for producing positive electrode active material particles according to one embodiment of the present invention. [Figure 5] Figures 5(A) to 5(D) illustrate a positive electrode according to one embodiment of the present invention. [Figure 6] Figures 6(A) and 6(B) illustrate a lithium-ion secondary battery according to one embodiment of the present invention. [Figure 7] Figures 7(A) to 7(C) illustrate a lithium-ion secondary battery according to one embodiment of the present invention. [Figure 8] Figures 8(A) to 8(D) illustrate a lithium-ion secondary battery and energy storage system according to one embodiment of the present invention. [Figure 9] Figures 9(A) to 9(C) illustrate a lithium-ion secondary battery according to one embodiment of the present invention. [Figure 10] Figures 10(A) to 10(C) illustrate a lithium-ion secondary battery according to one embodiment of the present invention. [Figure 11] Figures 11(A) to 11(C) illustrate an electric vehicle according to one embodiment of the present invention. [Figure 12]Figures 12(A) to 12(D) illustrate a transport vehicle according to one embodiment of the present invention. [Figure 13] Figures 13(A) to 13(C) illustrate a motorcycle and the like according to one embodiment of the present invention. [Figure 14] Figures 14(A) to 14(D) illustrate an electronic device, etc., according to one embodiment of the present invention. [Figure 15] Figures 15(A) through 15(D) show examples of space equipment. [Figure 16] Figures 16(A) to 16(D) are scanning electron microscope (SEM) images of a positive electrode active material according to one embodiment of the present invention. [Figure 17] Figures 17(A) to 17(C) show the charge and discharge curves of a secondary battery according to one embodiment of the present invention. [Figure 18] Figure 18 is a graph showing the charge-discharge cycle characteristics of a secondary battery according to one embodiment of the present invention. [Modes for carrying out the invention]

[0020] The following describes embodiments for carrying out the present invention with reference to drawings and other illustrations. However, the present invention is not limited to the following embodiments. It is possible to modify the embodiments for carrying out the invention without departing from the spirit of the present invention.

[0021] In this specification, space groups are expressed using international notation (or Hermann-Mauguin notation) Short notation. Crystal planes and crystal directions are expressed using Miller indices. While crystallographic notation uses superscripts to indicate space groups, crystal planes, and crystal directions, due to formatting constraints in this specification, a minus sign (-) may be placed before the number instead. Individual orientations within a crystal are represented by [ ], collective orientations representing all equivalent directions by < >, individual crystal planes by ( ), and collective planes with equivalent symmetry by {}. Furthermore, trigonal crystals represented by the space group R-3m are sometimes represented by a composite hexagonal lattice for easier understanding of the structure. In addition to (hkl), (hkil) may also be used as Miller indices, where i is -(h+k). In this specification, unless otherwise specified, crystal planes and other elements for the space group R-3m are expressed using a composite hexagonal lattice.

[0022] In this specification, when simply referring to a positive electrode active material or positive electrode active material particles, depending on the analytical method, it may refer to multiple positive electrode active material particles or to a single positive electrode active material particle. For example, in descriptions of scanning transmission electron microscopy-energy dispersive X-ray spectroscopy (STEM-EDX) line analysis, STEM-electron energy loss spectroscopy (STEM-EELS), and electron diffraction, unless otherwise specified, it refers to a single positive electrode active material particle. On the other hand, in the cases of X-ray photoelectron spectroscopy (XPS), X-ray diffraction (XRD), and various mass spectrometry methods, unless otherwise specified, it refers to multiple positive electrode active material particles.

[0023] In this specification, the term "particle" is not limited to spherical shapes (circular cross-sections), but includes individual particles with elliptical, rectangular, trapezoidal, triangular, rounded-corner quadrilateral, asymmetrical shapes, and other cross-sectional shapes. Furthermore, individual particles may have irregular shapes. In addition, the term "particle" alone includes both primary and secondary particles.

[0024] Furthermore, when describing the characteristics of positive electrode active material particles, it is not necessarily required that all particles possess those characteristics. For example, if 50% or more, preferably 70% or more, and more preferably 90% or more of three or more randomly selected positive electrode active material particles possess the desirable characteristics described later, it can be said that this sufficiently improves the characteristics of a secondary battery having such positive electrode active material particles.

[0025] Furthermore, the distribution of an element refers to the region in which that element is continuously detected within a non-noise range using a certain continuous analytical method. A region in which an element is continuously detected within a non-noise range can also be defined as a region in which the element is always detected when the analysis is performed multiple times.

[0026] Furthermore, the space group of a crystal structure is identified by methods such as XRD, electron diffraction, and neutron diffraction. Therefore, in this specification, "belonging to a certain space group," "being part of a certain space group," or "being a certain space group" can be rephrased as "being identified to a certain space group."

[0027] In this specification, a rock salt-type crystal structure refers to a cubic crystal structure in which cations and anions are arranged alternately. It can also be described as a crystal structure in which anions are arranged in cubic close-packing and cations occupy all octahedral positions. There may be one type of cation and one type of anion, or multiple types. There may also be vacancies in the cations or anions.

[0028] In this specification, the term "layered rock salt type crystal structure" refers to a crystal structure that shares with the rock salt type in that anions are arranged in cubic close-packed arrangement, and cations and anions are arranged alternately in octahedral positions, in addition to the presence of multiple types of cations, and in which the arrangement of at least one type of cation forms a two-dimensional plane. Such lithium-rich oxides and lithium-rich cathodes can also be called layered types. Layered lithium-rich oxides and lithium-rich cathodes can be called layered lithium-rich oxides, lithium-rich layered oxides, layered lithium-rich cathodes, lithium-rich layered cathodes, etc. If lithium ions form a two-dimensional plane, two-dimensional diffusion of lithium is possible. Defects such as cation or anion deficiencies may exist. Furthermore, the cubic close-packed arrangement of anions does not necessarily have to be theoretical, and distortion may occur depending on the type and / or arrangement of the cations.

[0029] Furthermore, in this specification, the term "disordered rock salt" crystal structure refers to a crystal structure that has a cubic crystal system, in which anions are arranged in cubic close-packed arrangement, and cations and anions are arranged alternately at octahedral positions, sharing commonalities with the rock salt type, but in addition, it is clear that multiple types of cations are present, and the arrangement of these cations is irregular. In lithium-rich cathode active material particles, an irregular arrangement of cations means that the ratio of the occurrence frequency of each cation species is almost constant at each cation site, and no significant difference is observed between cation sites. For example, in HAADF-STEM (High-angle Annular Dark Field Scanning TEM) images, there is no significant difference in the contrast of the cation sites. Defects such as vacancies of cations or anions may be present.

[0030] In this specification, the term "spinel type" refers to a crystal structure having a cubic crystal system, represented by the general formula AB2O4, in which anions are arranged in cubic close-packed arrangement and cations exist at octahedral and tetrahedral positions. The atomic ratio of cations at octahedral and tetrahedral positions is 2:1, but this atomic ratio does not need to be strictly defined. For example, it can be a:1 (where a is between 1.9 and 2.1). It is preferable to determine that a crystal structure is of the spinel type from, for example, STEM images, electron diffraction patterns, FFT (Fast Fourier Transform) patterns of TEM images or FFT patterns of STEM images, STEM-EELS, etc.

[0031] In all types of rock salt crystals—layered rock salt, disordered rock salt, and spinel—the anions are arranged in a cubic close-packed structure. Furthermore, if the anion arrangement is roughly close to cubic close-packed, it can be considered cubic close-packed. A cubic close-packed anion arrangement refers to a state where the anions of the second layer are placed on top of the voids of the anions in the first layer, and the anions of the third layer are positioned directly above the voids of the anions in the second layer, but not directly above the anions of the first layer. Therefore, the anions do not necessarily have to form a strictly cubic lattice. Also, since real crystals always have defects, the analytical results may not always match the theory. For example, in electron diffraction patterns or FFT patterns such as TEM images, spots may appear at positions slightly different from the theoretical positions. For example, if the orientation from the theoretical position is 5 degrees or less, or 2.5 degrees or less, it can be said that it adopts a cubic close-packed structure.

[0032] Furthermore, positive electrode active material particles to which additive elements that improve conductivity and / or additive elements that stabilize the crystal structure are added may be expressed as composite oxides, positive electrode materials, positive electrode materials, positive electrode materials for secondary batteries, etc. In addition, it is preferable that the positive electrode active material particles of one aspect of the present invention have a compound. In addition, it is preferable that the positive electrode active material particles of one aspect of the present invention have a composition. In addition, it is preferable that the positive electrode active material particles of one aspect of the present invention have a composite. Furthermore, a composite oxide refers to an oxide having multiple types of cations. A composite oxide has oxygen as an anion, but is not limited to oxygen alone, and may have other anions such as fluorine and chlorine in addition to oxygen.

[0033] As the charging voltage of a secondary battery increases, the voltage at the positive electrode generally rises. The positive electrode active material particles in one embodiment of the present invention have a stable crystal structure even at high voltages. Because the crystal structure of the positive electrode active material particles is stable in the charged state, the decrease in charge / discharge capacity due to repeated charging and discharging can be suppressed.

[0034] Unless otherwise specified, the materials of a secondary battery (positive electrode active material, negative electrode active material, electrolyte, separator, etc.) will be described in their state before degradation. Note that a decrease in discharge capacity due to aging and / or burn-in treatment during the secondary battery manufacturing process is not considered degradation. For example, a lithium-ion secondary single cell and lithium-ion secondary battery pack (hereinafter referred to as "lithium-ion secondary battery") can be considered to be in its pre-degradation state if it has a discharge capacity of 97% or more of its rated capacity. The rated capacity for lithium-ion secondary batteries for portable devices conforms to JIS C 8711:2019. For other lithium-ion secondary batteries, the specifications may conform to various JIS and IEC standards, including those for electric vehicle propulsion and industrial use, in addition to the above JIS standard.

[0035] (Embodiment 1) In this embodiment, the characteristics of the positive electrode active material particles of one aspect of the present invention will be described using Figures 1 and 2.

[0036] Positive electrode active material particles 100 according to one aspect of the present invention comprise lithium, a transition metal M, oxygen, and an additive element. The positive electrode active material particles 100 are preferably a compound obtained by adding the additive element to lithium-rich positive electrode active material particles.

[0037] [Lithium-rich positive electrode active material particles] The term "lithium-rich positive electrode active material particles" refers to a composite oxide having a composition represented by Li x M 2-x O2 (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti and Ru, and 1<x<2). A part of O may be substituted with other anions such as F and / or Cl.

[0038] Li x M 2-x As is clear from the representation O2 (1<x<2), the Li / M (atomic ratio) of the lithium-rich positive electrode active material particles is greater than 1. It is also preferable that the positive electrode active material particles 100 according to one aspect of the present invention, which are obtained by adding an additive element to the lithium-rich positive electrode active material particles, have a Li / M greater than 1.

[0039] Examples of the lithium-rich positive electrode active material particles include layered rock salt type composite oxides and disordered rock salt type composite oxides.

[0040] <Layered rock salt type> The layered rock salt type lithium-rich positive electrode active material particles (also referred to as lithium-rich layered oxides) include materials synthesized by mixing Li2MnO3 and LiMO2 (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti and Ru) at a fixed ratio. Examples of LiMO2 include LiCoO2, LiNiO2, and LiNi a Co b Mn c O2 (a+b+c=1) and the like. The crystal structure of the layered rock salt type may be referred to as layered or layered structure. Similarly, the layered rock salt type lithium-rich positive electrode active material particles may be referred to as layered lithium-rich positive electrode active material particles, lithium-rich layered positive electrode active material particles, or the like in some cases.

[0041] Li2MnO3 has a crystal structure with space group C2 / m symmetry, and LiMO2 has a crystal structure with space group R-3m symmetry. A material synthesized by mixing Li2MnO3 and LiMO2 in a fixed ratio becomes a solid solution with a P2 / m crystal structure, a C2 / m crystal structure, or an R-3m crystal structure. Alternatively, it becomes a composite structure having regions of C2 / m crystal structure and regions of R-3m crystal structure. Furthermore, this composite structure may have a region of P2 / m crystal structure in place of, or in addition to, either the C2 / m crystal structure region or the R-3m crystal structure region.

[0042] Li2MnO3 with space group C2 / m and LiMO2 with space group R-3m both have structures where the cation and anion are adjacent to each other, each occupying an octahedral position. Even when these solid solutions adopt a crystal structure with space group P2 / m, the cation and anion can each occupy an octahedral position. These structures are octahedrons with anions at the vertices and cations at the center that share edges, and can be described as distorted rock salt structures. Furthermore, when the cations are regularly arranged, these composite oxides having crystal structures with space group P2 / m, C2 / m, and / or R-3m can all have layered rock salt-type crystal structures.

[0043] Examples of layered rock salt-type lithium-rich cathode active material particles include 0.3Li2MnO3-0.7Li(Ni 1 / 3 Co 1 / 3 Mn 1 / 3 Li (also written as O2) 1.14 Mn 0.46 Ni 0.2 Co 0.2 O2, 0.5Li2MnO3-0.5Li(Ni 1 / 3 Mn 1 / 3 Co 1 / 3 Li (also written as O2) 1.2 Mn 0.54 Co 0.13 Ni 0.13 O2, 0.5Li2MnO3-0.5Li(Ni 1 / 2 Mn 1 / 2 Li (also written as O2) 1.2 Mn 0.6Ni 0.2 O2, and Li(Li, which is also denoted as LiCoO2-Li2MnO3 x / 3 Mn 2x / 3 Co 1-x )O2 (0≦x≦1), etc. can be used.

[0044] In particular, Li 1.2 Mn 0.6 Ni 0.2 O2, which contains Mn and Ni as the transition metal M, has an atomic ratio of Li / transition metal of 1.3 to 1.7, and an atomic ratio of Ni / (Mn+Ni) of 0.1 to 0.3, is preferable because it can achieve both a large discharge capacity exceeding 200 mAh / g and a relatively high discharge capacity retention rate during cycles.

[0045] <Disordered Rock Salt Type> The disordered rock salt type lithium-rich positive electrode active material particles are represented by the composition Li x M 2-x O2 (M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti and Ru, 1<x<2), and refers to a composite oxide having a rock salt type crystal structure and a disordered cation arrangement. A part of O may be substituted with other anions such as F and / or Cl.

[0046] Examples of combinations of elements contained in the disordered rock salt type lithium-rich positive electrode active material particles include Li-Cr-Mo-O, Li-Ti-Mn-O, Li-Ni-Mn-O, Li-Nb-Mn-O, Li-Nb-Fe-O, Li-Ti-Fe-O, Li-Ti-Ni-O, Li-V-O, Li-Nb-V-O, Li-V-O-F, Li-Mn-O-F, Li-Mo-O-F, etc.

[0047] [Additive Element] The positive electrode active material particles 100 preferably contain, as additive elements, one or more selected from magnesium, fluorine, titanium, aluminum, nickel, cobalt, manganese, zirconium, vanadium, iron, chromium, niobium, arsenic, zinc, silicon, sulfur, phosphorus, boron, bromine, and beryllium.

[0048] [Core-shell structure] Furthermore, as shown in Figure 1, the positive electrode active material particle 100 has a core 102 and a shell 101 outside the core 102.

[0049] Core 102 has the characteristics of lithium-rich cathode active material particles. For example, it has the same crystal structure and / or composition as lithium-rich cathode active material particles. Therefore, Core 102 preferably has a layered rock salt type or irregular rock salt type crystal structure and preferably has the composition described above.

[0050] The shell 101 contains more additive elements than the core 102. In other words, the shell 101 has a higher concentration and / or detectable amount of additive elements than the core 102. Furthermore, it is preferable that the concentration and / or detectable amount of additive elements are higher in the outer part of the shell 101.

[0051] For example, in XPS analysis, surface sensitivity increases when the photoelectron extraction angle is shallower, i.e., smaller, compared to when the photoelectron extraction angle is close to 90°. Therefore, when XPS analysis is performed on positive electrode active material particles 100 by changing the photoelectron extraction angle, it is preferable that the concentration and / or detection amount of the additive element is higher when the extraction angle is shallower than when the extraction angle is close to 90°.

[0052] When magnesium is used as an additive element, the atomic ratio of Mg / M (where M is the sum of one or more elements selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti, and Ru) when XPS analysis is performed on 100 positive electrode active material particles at an extraction angle of 45° is preferably 3% or more, more preferably 4% or more, and even more preferably 5% or more. When the analysis is performed at an extraction angle of 15°, the atomic ratio of Mg / M is preferably 3% or more, more preferably 5% or more, and even more preferably 7% or more.

[0053] When fluorine is used as an additive element, the atomic ratio of F / M when XPS analysis is performed on 100 positive electrode active material particles at an extraction angle of 45° is preferably 0.15 or higher, more preferably 0.20 or higher, and even more preferably 0.30 or higher. When the analysis is performed at an extraction angle of 15°, the atomic ratio of F / M is preferably 0.15 or higher, more preferably 0.25 or higher, and even more preferably 0.35 or higher.

[0054] However, if the concentration and / or detected amount of the additive element in shell 101 is too high, lithium diffusion may be inhibited, potentially leading to an increase in internal resistance, a decrease in charge / discharge capacity, and so on. Therefore, the concentration and / or detected amount of the additive element in XPS analysis is preferably twice or less the concentration and / or detected amount of lithium, and more preferably less than or equal to the concentration and / or detected amount of lithium.

[0055] When an element not present in the core 102 is used as an additive element, it is preferable that the element be detected in the shell 101 of the resulting positive electrode active material particles 100. When an element also present in the core 102 is used as an additive element, it is preferable that the element be detected in the core 102 of the resulting positive electrode active material particles 100, and that the concentration and / or amount detected in the shell 101 is higher than that of the core 102.

[0056] Since the shell 101 contains more additive elements than the core 102, its composition differs from that of the core 102. Therefore, it is preferable that the crystal structure of the shell 101 also differs from that of the core 102. For example, it is preferable that the shell 101 has a rock salt type, irregular rock salt type, or spinel type crystal structure.

[0057] However, the core 102 and the shell 101 may have the same crystal structure. For example, the core 102 and the shell 101 may both have a disordered rock salt crystal structure, although they may differ in the constituent elements and / or the ratios of the constituent elements.

[0058] The shell 101, which is a region including the surface of the positive electrode active material particles 100 or a region close to the surface, has a rock salt type or spinel type crystal structure containing many additive elements, which is expected to suppress side reactions with the electrolyte and / or electrolyte.

[0059] If the shell 101 is too thin, the surface and bulk of the positive electrode active material particles 100 may not be sufficiently stabilized. Therefore, the thickness of the shell 101 is preferably 1 nm or more, and more preferably 2 nm or more. It can also be 3 nm or more, or 5 nm or more. On the other hand, a thinner shell 101 tends to result in higher charge and discharge capacity. This is because the additive elements in the shell 101 may not contribute to the oxidation-reduction reaction of the secondary battery. Or, even if the additive elements in the shell 101 contribute to the oxidation-reduction reaction of the secondary battery, the crystal structure may result in lower charge and discharge capacity compared to lithium-rich positive electrode active materials. Furthermore, if the shell 101 is too thick, the electrical resistance and / or lithium-ion diffusion resistance may increase. For this reason, the thickness of the shell 101 is preferably 10 nm or less.

[0060] <Approximate alignment> When the crystal structures of the shell 101 and the core 102 are different, it is preferable that the orientations of the crystal structures of both are approximately the same. By having approximately the same orientation, a stable shell 101 can be obtained, and the detachment of oxygen from the core 102, the elution of cations, etc. can be more effectively suppressed.

[0061] In this specification, it is sometimes said that the crystal orientations are approximately identical when the orientations of the cubic close-packed structure composed of anions are aligned in rock salt type, layered rock salt type, disordered rock salt type, and spinel type. Furthermore, having a three-dimensional structural similarity such that the crystal orientations are approximately identical, or having the same crystallographic orientation, is called topotaxy.

[0062] The fact that the crystal orientations of the two regions roughly match can be determined from a TEM (Transmission Electron Microscope) image, a STEM (Scanning Transmission Electron Microscope) image, a HAADF-STEM image, an ABF-STEM (Annular Bright-Field Scanning Transmission Electron Microscope) image, an electron diffraction pattern, and the like. It can also be determined from the FFT pattern of a TEM image, and the FFT pattern of a STEM image or the like. Furthermore, XRD (X-ray Diffraction), neutron diffraction, and the like can also be used as criteria for the determination.

[0063] With TEM images, STEM images, and the like, images reflecting the crystal structure can be obtained. In addition, an electron diffraction pattern can provide information on the crystal orientation at each location. In particular, to obtain information on the crystal orientation in a narrow region, it is useful to use nanobeam electron diffraction as the electron diffraction method.

[0064] When the crystal planes of the layered rock salt and the rock salt structure match, the matching of the crystal planes can be observed by a high-resolution STEM image, an electron diffraction pattern, or the like. It is preferable to selectively use electron diffraction techniques such as selected area diffraction and nanobeam diffraction according to the size of the particles and / or the range of the rock salt structure of the shell 101.

[0065] For example, in a HAADF-STEM image, a contrast proportional to the atomic number is obtained, and an element with a larger atomic number can be observed brighter. For example, Li x M 2-x In the case of O2 (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti and Ru, 1<x<2), since M which is a transition metal has the largest atomic number, the electron beam is strongly scattered at the position of the transition metal M, and if there is an arrangement of the transition metal M, it can be observed as an arrangement of points with strong luminance.

[0066] Therefore, in HAADF-STEM images, when an electron beam is incident perpendicular to the c-axis of a layered rock salt composite hexagonal lattice, an array of brightly luminous points originating from the transition metal M on the (001) plane is obtained as a bright band (bright strip). Similarly, when an electron beam is incident perpendicular to the (111) plane of the rock salt, an array of points originating from the metallic elements on the (111) plane is obtained as a bright band. In this way, if repetitions of bright bands are observed in both regions of the STEM image, and the angle between the bright bands is 5 degrees or less or 2.5 degrees or less, or if the difference in spacing between multiple bright bands is within 15%, it can be determined that the crystal planes are roughly coincidental, that is, the crystal orientation is roughly coincidental.

[0067] Therefore, in HAADF-STEM images, if a sequence of highly luminous points, i.e., a bright band, is observed in two regions with different crystal structures, and the angle between these sequences is 5 degrees or less, or 2.5 degrees or less, or if the difference in the spacing between these sequences is within 15%, it can be determined that the crystal orientations are roughly consistent.

[0068] In ABF-STEM, elements with smaller atomic numbers may appear brighter, but since contrast is obtained according to atomic number, similar to HAADF-STEM, the orientation of the crystal can be determined in the same way as with HAADF-STEM images.

[0069] Furthermore, information about the crystal orientation for each region can be obtained from the FFT pattern of TEM images, the FFT pattern of STEM images, or the electron diffraction pattern. For example, the

[0001] direction in a region of layered rock salt structure having a crystal structure of space group C2 / m or R-3m, and the direction in a region of rock salt structure having a crystal structure of space group Fm-3m. <111> Information can be obtained regarding whether the directions are roughly consistent. If the crystal orientations coincide by 5 degrees or less, or by 2.5 degrees or less, it can be determined that the crystal planes roughly coincide, i.e., the crystal orientations roughly coincide.

[0070] In this case, it is preferable that these reciprocal lattice points are spot-like, that is, they do not form a concentric ring continuous with other reciprocal lattice points. The fact that the reciprocal lattice points are spot-like and not continuous with other reciprocal lattice points indicates high crystallinity.

[0071] Similarly, if the orientation of the irregular salt type and the salt type are roughly the same, then the two <111> The orientations may roughly coincide. Also, if the orientations of irregular salt deposits and spinel deposits roughly coincide, then the two... <111> The orientations may roughly coincide. Also, if the orientations of the layered salt type and the spinel type roughly coincide, then the two <111> The directions may roughly coincide.

[0072] It is known that layered rock salt type positive electrode active material particles of space group R-3m tend to exhibit (001) planes and equivalent planes, as well as (104) planes and equivalent planes, as crystal planes. Therefore, when observing the (001) plane with a TEM, for example, it is preferable to first select positive electrode active material particles in which the crystal plane expected to be the (001) plane can be observed using an SEM, and then to thin-section these positive electrode active material particles using a FIB (Focused Ion Beam), for example, so that the (001) plane can be observed with the electron beam incident at

[0120] in a TEM. When it is desired to determine the consistency of the crystal orientation, it is preferable to thin-section the particle so that the (001) plane of the layered rock salt type is easily observable. Similarly, in the case of positive electrode active material particles with other crystal structures, it is preferable to thin-section the particle so that the arrangement of the transition metal M is easily observable.

[0073] The approximate agreement of the crystal structures of the shell 101 and the core 102 allows the shell 101, which contains many additive elements, to function as a pillar supporting the crystal structure of the positive electrode active material particles 100. Among the additive elements, magnesium is particularly preferred because its strong bonding with oxygen is expected to provide high functionality as a pillar for the positive electrode active material particles 100. In other words, the presence of additive elements stabilizes the crystal structure of the surface and / or bulk of the positive electrode active material particles 100. Therefore, changes in the crystal structure and / or oxygen detachment during charging of the positive electrode active material particles 100 can be suppressed.

[0074] Therefore, the positive electrode active material particles 100 can be such that the decrease in the initial discharge capacity relative to the initial charge capacity is suppressed, or that the positive electrode active material particles 100 have good rate characteristics, or that the decrease in voltage or discharge capacity during the charge-discharge cycle is suppressed.

[0075] <Examples of roughly matching orientations> For the crystal structures of shell 101 and core 102 to be different and their orientations to be roughly the same, it is necessary that the anion packing structure is common and that there is no large mismatch in the lattice constants of the two. More precisely, considering cases where the space groups are different, it is necessary that there is no large mismatch in the metal-to-metal distance and the interlayer distance. Here, the metal-to-metal distance is the average of the distances between nearest metal atoms in the same layer. The interlayer distance is the average distance between two metal layers. A metal layer is a plane in which metal atoms are arranged, and in the case of rock salt structures and disordered rock salt structures (Fm-3m), it is the (111) plane. In the case of layered rock salt structures, it is the (001) plane for R-3m, the (001) plane for C / 2m, and the (001) plane for P2 / m. In the case of spinel structures (Fd-3m), it is the (111) plane. When there are multiple types of metals and they are arranged regularly, the plane in which the most of the same type of metal is arranged may be called a metal layer.

[0076] If the relative values ​​of the metal-to-metal distance and the interlayer distance of the core 102 to the shell 101 are between 0.94 and 1.06, then the crystal structures can be roughly matched.

[0077] The following are examples where the crystal structures of the shell 101 and core 102 are different, but their crystal orientations may be roughly the same.

[0078] First, we will describe an example in which the core 102 has the crystalline structure and composition of layered rock salt-type lithium-rich cathode active material particles, and the shell 101 has a rock salt-type crystalline structure.

[0079] Since layered rock salt type lithium-rich cathode active material particles are synthesized by mixing Li2MnO3 and LiMO2 (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti, and Ru) in a fixed ratio, the metal-to-metal distance and interlayer distance of core 102 are expected to be one of the values ​​between Li2MnO3 and LiMO2. Table 1 shows experimental values ​​of known metal-to-metal distance and interlayer distance for Li2MnO3. Similarly, known examples of LiMO2 include LiCoO2, LiNiO2, and LiNi 1 / 2 Mn 1 / 2 O2 and LiNi 1 / 3 Mn 1 / 3 Co 1 / 3 The experimental values ​​for O2 are shown. All values ​​are given to four significant figures, with interlayer distances between 2.342 Å and 2.382 Å, and metal-to-metal distances between 2.816 Å and 2.887 Å.

[0080] [Table 1]

[0081] Figure 2(A) shows a schematic diagram of the (001) plane of the crystal structure of Li2MnO3 with space group C2 / m in the upper panel, and a schematic diagram of the (010) plane perpendicular to the (001) plane in the lower panel. The (001) plane of the Li2MnO3 crystal structure is the plane in which the metal is arranged in layers. To make the diagram clearer, the (001) plane in the upper panel of Figure 2(A) shows an excerpt of one metal layer and the oxygen layers above and below it. In the (010) plane in the lower panel, only the one metal layer and the oxygen layers above and below it show bonding.

[0082] The crystal structure of Li2MnO3 in ICSD Collection Code: 73370 contains both a layer with a mixture of Li and Mn as metallic layers, and a layer with only Li. Both layers are parallel or approximately parallel to the a-axis and b-axis. Furthermore, the metallic sites in the layer with a mixture of Li and Mn are partially occupied by Li and Mn. However, for the sake of simplicity, Figure 2(A) shows the element with the larger occupancy as a representative example in the layer with a mixture of Li and Mn. Because the metallic sites of Li2MnO3 are deviated from an equilateral triangle arrangement, the metal-to-metal distances in Li2MnO3 can be determined by the following two methods.

[0083] One method involves determining the intermetallic distance by averaging the distances between metal atoms in a mixed layer of Li and Mn. The layer containing only Li was not used in the calculation because the atomic positions are slightly offset from the same plane. The resulting metal-to-metal intermetallic distance was 2.842 Å to four significant figures.

[0084] Another approach is to assume that when the distance between metals is x, the length of the a-axis is 4.921 Å, which is (√3)x, and the length of the b-axis is 8.526 Å, which is 3x. Then, the product of the lengths of the a-axis and b-axis is 41.95645 Å. 2 is 3(√3)x 2 This is a method for calculating x when the result is as follows. The metal-to-metal distance obtained using this method was 2.842 Å to four significant figures. Thus, the metal-to-metal distances obtained using the two methods were the same to four significant figures.

[0085] Figure 2(B) shows a schematic diagram of the (001) plane of the crystal structure of LiCoO2, which has the space group R-3m, as an example of LiMO2, in the upper panel, and a schematic diagram of the (110) plane perpendicular to the (001) plane in the lower panel. The (001) plane of the LiCoO2 crystal structure is the plane in which the metal is arranged in layers. To make the diagram clearer, the (001) plane in the upper panel of Figure 2(B) shows an excerpt of one metal layer and the oxygen layers above and below it. In the (110) plane in the lower panel, only the one metal layer and the oxygen layers above and below it show bonding.

[0086] Since the concentration and / or detected amount of the additive elements are higher in shell 101 than in core 102, the metal-to-metal distance and interlayer distance of shell 101 are thought to be between the values ​​for the rock salt-type oxide of the additive elements and the crystal structure of core 102. Here, magnesium, cobalt, nickel, and manganese are taken as examples of additive elements, and Table 1 shows experimental values ​​for the metal-to-metal distance and interlayer distance of known MgO, CoO, NiO, and MnO. The interlayer distance and metal-to-metal tube distance of the rock salt-type oxide are both given to four significant figures, with the interlayer distance being between 2.412 Å and 2.567 Å, ​​and the metal-to-metal distance being between 2.954 Å and 3.144 Å.

[0087] Figure 2(C) shows a schematic diagram of the (111) plane of the crystal structure of MgO, with space group Fm-3m, as an example of a rock salt-type oxide with added elements, in the upper panel, and a schematic diagram of the (-110) plane perpendicular to the (111) plane in the lower panel. The (111) plane of the MgO crystal structure is the plane in which the metal is arranged in layers. To make the diagram clearer, the (111) plane in the upper panel of Figure 2(C) shows an excerpt of one metal layer and the oxygen layers above and below it. In the (-110) plane in the lower panel, only the one metal layer and the oxygen layers above and below it show bonding.

[0088] As shown in Figures 2(A) to 2(C), these oxides, although belonging to different space groups, share the common features of cubic close-packed oxygen and alternating arrangement of cations and anions. Furthermore, as indicated by the dotted lines in Figures 2(A) to 2(C), the cations are all located in 6-coordinate octahedral positions.

[0089] Table 1 shows the relative values ​​of the metal-to-metal and interlayer distances in MgO, with each distance set to 1. Note that for Li2MnO3 and LiCoO2, the interlayer distance varies depending on the position of the layer, so the average value is shown.

[0090] When the metal-to-metal distance and interlayer distance of MgO are set to 1, the relative values ​​of the interlayer distance and metal-to-metal distance are both between 0.94 and 1.06, clearly indicating that there is no significant mismatch between these crystal structures. Therefore, if the core 102 has the composition and crystal structure of the layered rock salt type lithium-rich cathode active material particles exemplified above, and the shell 101 has magnesium, cobalt, nickel and / or manganese as additive elements and has a rock salt type crystal structure, the crystal structures of the shell 101 and the core 102 can be approximately identical.

[0091] Next, we will describe an example in which the core 102 has the crystal structure and composition of irregular rock salt-type lithium-rich cathode active material particles, and the shell 101 has a rock salt-type crystal structure. Since the irregular rock salt-type crystal structure of the core 102 is the same as the rock salt-type crystal structure of the shell 101, the two can be compared using lattice constants.

[0092] Non-patent document 5 describes a lithium-rich cathode active material having an irregular rock salt-type crystal structure. 1.05 Mn 0.85 Ti 0.1 O2, Li 1.10 Mn 0.70 Ti 0.2 O2 and Li 1.15 Mn 0.55 Ti 0.3 It has been shown that the lattice constant a of O2 is between 4.16 Å and 4.17 Å.

[0093] Here, we will take magnesium as an example of an additive element. The lattice constant a of MgO is 4.217 Å.

[0094] From these findings, it is clear that the lattice constant a of the irregular rock salt type lithium-rich cathode active material particles is between 0.986 and 0.989, and that there is no significant mismatch between these crystal structures.

[0095] Therefore, if the core 102 has the composition and crystal structure of the irregular rock salt type lithium-rich cathode active material particles exemplified above, and the shell 101 has magnesium as an additive element and has a rock salt type crystal structure, the crystal orientations of the shell 101 and the core 102 can be approximately the same.

[0096] Next, we will describe an example in which the core 102 or shell 101 has a spinel-type crystal structure. When evaluating the approximate agreement of crystal orientation between the spinel type and other crystal structures, it is preferable to compare oxygen stacking with the relative interlayer distance of the oxygen layers.

[0097] An example of a spinel-type structure (space group: Fd-3m) containing Li and Mn is the crystal structure of LiMn2O4, ICSD Collection Code: 73370. In spinel-type structures, oxygen is stacked in a cubic close-packed manner. <111> The pattern is ABCABC... stacking in a specific direction.

[0098] The rock salt-type oxygen is also cubically close-packed. <111> The stacking pattern is ABCABC… relative to the direction. The oxygen layer of the layered rock salt type R-3m is also cubic close-packed, and the stacking pattern is ABCABC… relative to the direction

[0001] . The oxygen layer of the layered rock salt type C / 2m is also cubic close-packed, and the stacking pattern is generally ABCABC… relative to the direction perpendicular to the c-plane.

[0099] Therefore, if the interlayer distance and oxygen-to-oxygen distance in the stacking of oxygen layers in spinel-type LiMn2O4 are consistent, the crystal orientation will roughly match that of rock salt structures (Fm-3m) and layered rock salt structures (R-3m, C / 2m).

[0100] In the rock salt crystal structure of space group Fm-3m, the metal-to-metal distance is the same as the oxygen-to-oxygen distance. Similarly, the interlayer distance of the metal layer is the same as the interlayer distance of the oxygen layer. In layered rock salt structures of space group R-3m, such as LiCoO2, the metal-to-metal distance is the same as the oxygen-to-oxygen distance. In layered rock salt structures such as LiCoO2, oxygen and metal are arranged alternately, and the average interlayer distance of the metal layer is the same as the average interlayer distance of the oxygen layer. In Li2MnO3, oxygen and metal are arranged alternately in the direction perpendicular to the (001) plane, and the average interlayer distance of the metal layer is the same as the average interlayer distance of the oxygen layer. In layered rock salt structures of space group C / 2m, the latter method described above for determining the metal-to-metal distance can also be applied to determining the oxygen-to-oxygen distance. That is, the oxygen-to-oxygen distance within the same plane is the same as the previously determined metal-to-metal distance. Therefore, it can be said that the metal-to-metal distances shown in Table 1 are the same as the oxygen-to-oxygen distances. Similarly, the interlayer distance of the metal layer can be said to be the same as the interlayer distance of the oxygen layer.

[0101] The oxygen atoms in the (111) plane of LiMn2O4 are offset from the triangular lattice points. Therefore, assuming that the oxygen atoms are positioned so that they occupy the same plane as the triangular lattice points, we can assume the distance between the triangular lattice points is the oxygen-oxygen distance. Under this assumption, the calculated oxygen-oxygen distance is 2.908 Å, and its relative value to the oxygen-oxygen distance of MgO is 0.98.

[0102] Since the oxygen positions in LiMn2O4 are offset from the (111) plane, we similarly take the average of each oxygen position on the (111) plane as the oxygen position on the (111) plane, and assume that the distance of the oxygen layer in the

[0111] direction, obtained using the oxygen positions on the (111) plane, is the interlayer distance of the oxygen layer. Under this assumption, the calculated interlayer distance of the oxygen layer is 2.375 Å, and its relative value to the interlayer distance of the oxygen layer of MgO is 0.98. Thus, for LiMn2O4, both the oxygen-to-oxygen distance and the interlayer distance of the oxygen layer are in the range of 0.94 to 1.06 relative to MgO.

[0103] Therefore, if the core 102 has a spinel-type structure such as LiMn2O4, the crystal orientation may roughly coincide with that of the rock salt-type shell 101 containing Mg. Also, if the shell 101 has a spinel-type structure such as LiMn2O4, the crystal orientation may roughly coincide with that of the core 102 having a layered rock salt-type and / or disordered rock salt-type crystal structure.

[0104] The particle size of the positive electrode active material particles 100 is preferably 500 nm or less in diameter, more preferably 250 nm or less, and even more preferably around 100 nm, in order to suppress the diffusion resistance of lithium within the particles. On the other hand, if the particle size is too small, disadvantages such as aggregation may occur. Therefore, the diameter is preferably 25 nm or more, and more preferably 50 nm or more.

[0105] Furthermore, unless otherwise specified in this specification, the characteristics of the primary particles of the positive electrode active material particles 100 will be described, but the positive electrode active material particles may also have secondary particles formed by aggregation, adhesion, and / or sintering of multiple primary particles. Having secondary particles is preferable because it increases the particle size and facilitates coating onto the current collector, etc.

[0106] When the positive electrode active material particles 100 have secondary particles, a shell 101 may be formed for each primary particle contained within the secondary particle. Alternatively, the shell 101 may be formed on the secondary particle as a single particle. In other words, there may be primary particles inside the secondary particle that do not have a shell 101. Furthermore, additive elements may be used as sintering aids when granulating primary particles into secondary particles.

[0107] While it is preferable for the shell 101 to have a rock salt type or spinel type crystal structure, the shell 101 does not necessarily have to be the only one to have a rock salt type or spinel type crystal structure. For example, a part of the core 102 may have a rock salt type or spinel type crystal structure.

[0108] Furthermore, the shell 101 does not necessarily need to cover the entire surface of the positive electrode active material particles 100. However, in order to function as a pillar, it is preferable that the shell 101 covers 50% or more, preferably 70% or more, and more preferably 90% or more, of the surface of the positive electrode active material particles 100.

[0109] Furthermore, the shell 101 does not have to be entirely of the rock salt type or spinel type crystalline structure. For example, it may be partially amorphous or have other crystalline structures. Similarly, the core 102 does not have to be entirely of the layered rock salt type or disordered rock salt type crystalline structure. For example, it may be partially amorphous or have other crystalline structures.

[0110] [analysis] <Composition> The composition of the positive electrode active material particles 100 in one aspect of the present invention is preferably evaluated by combining multiple analyses. For example, among the elements present in the positive electrode active material particles 100, it is preferable to determine the ratio of the main components, lithium, transition metal M, and oxygen, using ICP-MS (inductively coupled plasma mass spectrometry) or the like. For the additive elements, it is preferable to determine the ratio using an analysis sensitive to trace elements, such as GD-MS (glow discharge mass spectrometry).

[0111] <Distribution of added elements> The distribution of additive elements in the positive electrode active material particles 100 according to one aspect of the present invention is preferably evaluated, for example, by cross-sectional analysis of the positive electrode active material particles 100.

[0112] For example, cross-sectional STEM-EDX is preferred because of its high spatial resolution. To further increase the spatial resolution in STEM-EDX radiation analysis, it is preferable to have a small electron beam diameter (also called beam diameter, probe diameter, or probe diameter). In STEM-EDX radiation analysis, the beam diameter is preferably 0.3 nm or less, more preferably 0.2 nm or less, and even more preferably 0.1 nm or less.

[0113] Furthermore, cross-sectional EPMA (electron probe microanalyzer) is preferable because it has a low detection limit for elements.

[0114] Multiple analyses can be combined and evaluated as needed.

[0115] The interface between the shell 101 and the core 102 is defined as a series of points that show a detection amount closest to half the sum of the detection amount of the additive element in the center of the positive electrode active material particle 100 and the detection amount of the part near the surface of the positive electrode active material particle 100 that is detected most abundantly. If there are multiple additive elements, the element that is easiest to detect and / or quantify is selected based on the composition of the positive electrode active material particle 100. For example, if there is an additive element that is not contained in the core 102, it is preferable to select that element. It is also preferable to select an element whose characteristic X-ray spectrum overlaps less with the elements present in the core 102. Furthermore, it is preferable to select an element that is detected more abundantly near the surface.

[0116] <Surface> In one embodiment of the present invention, the positive electrode active material particles are compounds having a transition metal M and oxygen that can undergo lithium insertion and deinsertion. Therefore, in this specification, the interface between the region where the transition metal M and oxygen that undergo oxidation and reduction with lithium insertion and deinsertion are present and the region where they are absent is considered the surface of the positive electrode active material particles. Surfaces formed by slip, cracks, and / or fissures may also be considered the surface of the positive electrode active material particles. When the positive electrode active material particles are subjected to analysis, a protective film may be applied to the surface, but the protective film is not included in the positive electrode active material particles. As the protective film, a single-layer or multi-layer film of carbon, metal, oxide, resin, etc. may be used.

[0117] For similar reasons, the positive electrode active material particles of one embodiment of the present invention do not contain metal oxides that do not have lithium sites that can contribute to charging and discharging, such as aluminum oxide (Al2O3), nor do they contain carbonates, hydroxyl groups, etc., that are chemically adsorbed after the production of the positive electrode active material particles. The adhering metal oxides refer to, for example, metal oxides whose crystal structure does not substantially match that of lithium-rich positive electrode active material particles.

[0118] Furthermore, electrolytes, organic solvents, binders, conductive materials, or compounds derived from these that adhere to the positive electrode active material particles are not included in the positive electrode active material particles.

[0119] In STEM-EDX radiation analysis, due to the principle or measurement errors, the graph of the detected characteristic X-rays of an element may not show a steep change, making it difficult to precisely determine the surface. Therefore, when referring to the depth direction in STEM-EDX radiation analysis, the detected amount of characteristic X-rays of the transition metal M is considered to be equal to the average value M of the detected characteristic X-rays of the transition metal M inside the surface. AVE And the average value M of the detected characteristic X-rays of the above transition metal M in the background. BG The point where the sum of the two is 50%, or where the amount of oxygen characteristic X-rays detected is equal to the average value of the amount of oxygen characteristic X-rays detected inside O AVE And the average value of the detected characteristic X-rays of background oxygen O BG The reference point is the point at which the sum of the two values ​​is 50%. Note that if the point at which the detected amount of characteristic X-rays of the transition metal M is 50% of the sum of the average detected amount of characteristic X-rays of the internal transition metal M and the average detected amount of characteristic X-rays of the background transition metal M is different from the point at which the detected amount of characteristic X-rays of oxygen is 50% of the sum of the average detected amount of characteristic X-rays of internal oxygen and the average detected amount of characteristic X-rays of background oxygen, it is thought to be due to the influence of oxygen-containing metal oxides, carbonates, etc. adhering to the surface, and therefore the point at which the detected amount of characteristic X-rays of the transition metal M is 50% of the average detected amount of characteristic X-rays of internal transition metal M AVE And the average value M of the detected characteristic X-rays of the above transition metal M in the background. BG The point at 50% of the sum of these can be adopted as the reference point. In the case of positive electrode active material particles 100 having multiple transition metals M, the transition metal element M that has the highest amount of characteristic X-ray detection inside is selected. AVE and M BG The above reference points can be determined using this method.

[0120] The average value M of the detected characteristic X-rays of the above transition metal M in the background. BGFor example, the average value M of the detected characteristic X-rays of the transition metal M can be determined by averaging the range of 2 nm or more, preferably 3 nm or more, outside the positive electrode active material particles 100, while avoiding the vicinity where the detection amount of characteristic X-rays of the transition metal M begins to increase. AVE The average value of the background characteristic X-ray O is obtained by averaging a range of 2 nm or more, preferably 3 nm or more, more preferably 10 nm or more, from the region where the detection amount of characteristic X-rays of transition metal M and oxygen saturates and stabilizes, for example, from the region where the detection amount of characteristic X-rays of transition metal M begins to increase, to a depth of 30 nm or more, preferably beyond 50 nm. BG and the average value of the amount of characteristic X-rays detected from the internal oxygen O AVE This can be calculated in a similar manner.

[0121] Furthermore, the surface of the positive electrode active material particles in cross-sectional STEM (scanning transmission electron microscope) images, etc., is defined as the boundary between the region where an image originating from the crystal structure of the positive electrode active material particles can be observed and the region where it cannot be observed, and is the outermost region where atomic columns originating from the nuclei of metal elements with atomic numbers greater than lithium among the metal elements constituting the positive electrode active material particles can be confirmed. The surface in STEM images, etc., may also be determined in conjunction with analyses that have higher spatial resolution.

[0122] STEM observation and STEM-EDX radiation analysis are performed on thin section samples. Thin section samples are prepared by forming a protective film on the surface of the positive electrode active material and then performing a thin sectioning process.

[0123] Carbon can be used as the protective film. The carbon film can be formed by depositing carbon using the carbon coating unit of an ion sputtering apparatus. Alternatively, it can be formed by depositing carbon using FIB. Carbon films formed using FIB are preferable for oxide analysis because they contain less oxygen.

[0124] Thinning can be performed, for example, using a FIB-SEM device (Hitachi High-Tech NX5200). In this process, it is preferable to pick up the sample using an MPS (microprobing system) and to gradually reduce the acceleration voltage from high to low in the order of 30kV, 10kV, 5kV, (or 2kV) to remove the processing damage layer while finishing the sample. It is also preferable to measure the areas of the thinned sample that have little depth and unevenness.

[0125] For EDX measurements of the surface layer of positive electrode active material particles, it is preferable to use a magnification that allows sufficient information to be obtained within a few nanometers from the surface. For example, it is preferable to use a magnification that results in an electron beam scanning pitch of approximately 0.3 nm for EDX surface analysis, which corresponds to a measurement magnification of about 160,000 times (320,000 times on the screen display due to drift correction).

[0126] For elemental quantification in STEM-EDX analysis, a standardless quantification method using the k-factor, an element-specific coefficient built into the analytical instrument and / or analytical software, can be employed. Furthermore, when determining elemental concentrations from the quantification results, it is preferable that the target elements (also called the denominator elements) include the elements used in the target material, raw materials, mesh on which the thin section sample is placed, instrument components, and thin section processing. For example, it is preferable that the target elements be the 15 elements C, O, F, Mg, Al, Si, P, S, Ca, Ti, Mn, Fe, Co, Ni, and Ga. Net counts (indicating the total number of detected counts) and concentration can be optionally output. Also, when simply referring to the detected amount for a given element, it includes the characteristic X-ray count and concentration. Concentration can include both weight% and atomic%.

[0127] Furthermore, the spatial resolution of STEM-EDX depends on the probe diameter. Therefore, the maximum value of the additive element profile may shift by about 1 nm depending on conditions such as the probe diameter. For example, even if the maximum value of the additive element profile, such as magnesium, is outside the surface determined above, if the difference between the maximum value and the surface is less than 1 nm, it can be considered an error.

[0128] Furthermore, in STEM-EDX radiation analysis, a peak refers to the maximum value of a convex shape appearing on the graph of characteristic X-ray detection amounts for each element, or the maximum value of characteristic X-rays for each element. Noise in STEM-EDX radiation analysis can include measurements with a width at half maximum (FWHM) below the spatial resolution (R), for example, R / 2 or less.

[0129] The effects of noise can be reduced by scanning the same area multiple times under the same conditions, or by increasing the number of frames.

[0130] <Particle size distribution analysis using cross-sectional SEM images of the positive electrode> For example, the particle size distribution of the positive electrode active material particles 100 can be calculated from a cross-sectional SEM image of the positive electrode active material particles 100 using the method described below.

[0131] First, from the acquired cross-sectional SEM image, an analysis region is extracted so that sufficient cross-sections of the positive electrode active material particles 100 can be obtained for image analysis. For example, it is preferable to extract a region in which 100 or more cross-sections of the positive electrode active material particles 100 can be obtained.

[0132] Furthermore, image processing software functions may be used to crop the cross-sectional SEM image. For example, ImageJ may be used as the image processing software, and the crop function may be used to crop the image.

[0133] Next, the first image extracted using image processing software is binarized, and particle analysis is performed.

[0134] Image processing software such as ImageJ can be used. The binarization process is described below. The first image, shown in 256-value grayscale, is used as a frequency graph excluding black (value 0) and white (value 255). The low-value side (HWHM_L) and high-value side (HWHM_H) are determined as the half-width at half maximum (HWHM) of the maximum peak in this frequency graph. Next, from the value that is the peak top (maximum frequency) of the maximum peak, the lowest value a of the range that is twice the width of HWHM_L on the low-value side and the highest value b of the range that is twice the width of HWHM_H on the high-value side are determined.

[0135] Next, the image is binarized so that values ​​less than a are white, values ​​between a and b are black, and values ​​greater than b are white. Specifically, the ImageJ Threshold function is used to perform binarization as Threshold(a,b). Then, random bright spots thought to be caused by conductive materials are removed using the conditions Gray Morphology (radius=3,operator=open,type=circle) and Gray Morphology (radius=1,operator=close,type=circle), and a second image can be obtained.

[0136] Next, using the second image, the Analyze Particles function in ImageJ was used to determine the particle size (projected area) of 0.5 μm. 2 More than 700μm 2 The following particles are detected, and the area S of each particle is obtained. Next, the diameter r of each particle is calculated based on the area S of each particle (Equation 1).

[0137]

number

[0138] In this way, the particle size distribution can be calculated from the cross-sectional SEM image. Performing the above analysis is called performing particle size distribution analysis using the cross-sectional SEM image of the positive electrode.

[0139] This embodiment can be appropriately combined with the contents of other embodiments.

[0140] (Embodiment 2) In this embodiment, an example of the method for producing positive electrode active material particles according to one aspect of the present invention will be described with reference to FIGS. 3(A) to 4.

[0141] [Production Method 1] First, with reference to FIG. 3(A), Li x M 2-x An example of a method of synthesizing O2 (M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti, and Ru, 1<x<2) and then adding an additive element source will be described. Li x M 2-x The method for synthesizing O2 is not particularly limited, but in this embodiment, an example in which a solid-phase method is adopted will be described.

[0142] First, as step S11 in FIG. 3(A), a lithium (Li) source and an M source are prepared. As the lithium source, for example, lithium carbonate (Li2CO3), lithium hydroxide (LiOH) and / or lithium oxide (Li2O) or the like can be used. As the M source, an oxide, hydroxide, carbonate or the like of transition metal M can be used. For example, manganese oxide (Mn2O3, MnO2 and / or MnO), manganese carbonate (MnCO3), nickel oxide (NiO2), nickel carbonate (NiCO3), nickel hydroxide (Ni(OH)2), cobalt oxide (Co2O3), cobalt hydroxide (Co(OH)2), chromium oxide (Cr2O3), molybdenum dioxide (MoO2), niobium oxide (NbO, Nb2O5), vanadium oxide (V2O3), iron oxide (Fe2O3), titanium oxide (TiO2), ruthenium oxide (RuO2) and the like can be used.

[0143] Next, in step S12, the lithium source and the M source are mixed to prepare the first mixture 901 (step S13). Grinding during the mixing process is useful for reducing the particle size. It is preferable to use a bead mill and / or a ball mill for grinding. A planetary ball mill can be used as the ball mill. The bead mill and / or ball mill may be dry or wet. If heat is generated during mixing and grinding, it is preferable to perform the process while cooling.

[0144] Next, in step S14, the first mixture 901 prepared above is heated. A higher heating temperature allows for a shorter heating time and thus higher productivity. However, if the heating temperature is too high, the particle size may increase due to sintering of particles, potentially reducing the charge-discharge capacity. Furthermore, transition metals may become more easily reduced; for example, Mn may be reduced from tetravalent to trivalent, making it impossible to synthesize a composite oxide with the intended composition. While a shorter heating time is preferable for higher productivity, if the heating time is too short, the reaction may be insufficient. Therefore, the heating temperature is preferably, for example, 700°C to 1200°C, more preferably 800°C to 1050°C, and even more preferably 850°C to 950°C. The heating time is preferably, for example, 15 minutes to 100 hours, and more preferably 2 hours to 20 hours. If multiple heating steps are performed, the conditions must be such that appropriate synthesis occurs throughout the entire manufacturing process. Since this manufacturing method has two heating steps, step S14 and step S33, it is preferable that the heating temperature per step is lower and / or the heating time is shorter compared to a method that uses only one heating step. For example, it is more preferable that the heating temperature in step S14 is 950°C or lower.

[0145] By using the above heating conditions, the increase in particle size of Li was suppressed. x M 2-x O2 can be produced. Note that the heating time referred to here is the time during which the heating temperature is maintained, and does not include the time spent during heating and cooling.

[0146] For the heating furnace, for example, a muffle furnace, roller hearth kiln, rotary kiln, etc., can be used. For the container that holds the material to be heated, an aluminum oxide crucible or an aluminum oxide setter (also called a sheath) can be used. It is preferable to cover the crucible or setter before heating to prevent evaporation of the material. Mullite-cordierite may also be used as the material for the crucible and setter.

[0147] Layered rock salt type Li x M 2-x When producing O2, it is preferable to heat it in an oxygen-containing atmosphere. Irregular rock salt type Li x M 2-x When producing O2, it is preferable to heat it in an inert atmosphere such as argon or nitrogen.

[0148] In this heating process, if the amount of the first mixture 901 per heating container is too large, the first mixture 901 may not be able to come into sufficient contact with the atmosphere, potentially resulting in insufficient reaction in some areas. Therefore, it is preferable to heat the mixture in multiple heating containers as needed. If the mixture is heated in multiple heating containers, these containers should be mixed after heating. A bead mill, ball mill, mortar and pestle, mixer, and / or mixer can be used for this mixing.

[0149] In the above process, Li x M 2-x A composite oxide 902 represented by O2 is obtained (step S16).

[0150] Next, in step S23, a source of additive element (A) is prepared. In this specification, the term "additive element" is synonymous with "mixture" or "part of the raw materials." As the additive element source, either individual additive elements or compounds of additive elements can be used.

[0151] When magnesium is used as an additive element, magnesium oxide (MgO) and / or magnesium fluoride (MgF2) can be used as the magnesium source. When fluorine is used as an additive element, the fluorine source is preferably a fluoride of a typical metal element, and lithium fluoride (LiF), sodium fluoride (NaF), potassium fluoride (KF), and / or magnesium fluoride (MgF2) can be used. Considering its use in lithium-ion secondary batteries, lithium fluoride is particularly preferred as the fluorine source.

[0152] The fluorides of these typical metal elements can act as fluxes in the subsequent heating process, promoting the diffusion and doping of the added elements in the shell 101. The mixture containing the fluorides has a melting point of Li x M 2-x The decomposition temperature may be lower than that of the composite oxide represented by O2, and it is preferable because it is safer. In particular, mixtures of combinations such that the eutectic point in an oxygen-containing atmosphere is 1000°C, preferably 900°C or lower, are preferable because they tend to become liquid at relatively low temperatures.

[0153] Furthermore, since fluorine may be lost due to volatilization or other factors after functioning as a flux, even if fluorine is added as an additive element, it is possible that fluorine may not be detected in the positive electrode active material particles 100 after fabrication.

[0154] Next, in step S31, the composite oxide 902 and the additive element source are mixed to prepare a second mixture 903 (step S32). The mixing can be described in step S12.

[0155] Next, in step S33, the second mixture is heated. If the heating temperature is too low, doping with the additive elements may become uneven and / or insufficient. For this reason, a heating temperature of 500°C or higher is preferable, 700°C or higher is more preferable, and 850°C or higher is even preferable. On the other hand, if the temperature is too high, the composite oxide 902 may decompose, the particles may sinter and the particle size may become larger than necessary, so a heating temperature of 1050°C or lower is preferable. Furthermore, to suppress the volatilization of fluorides, including lithium fluoride, a temperature of 950°C or lower is more preferable. Based on the above, the heating temperature in step S33 is typically preferably between 850°C and 950°C.

[0156] Shorter heating times result in higher productivity, but if they are too short, the diffusion and doping of the added elements may be insufficient. The heating time is preferably between 15 minutes and 100 hours, and more preferably between 2 hours and 20 hours.

[0157] In the heating step S33, the composite oxide 902 and the additive element source partially melt, and the additive elements, including magnesium, are effectively diffused and doped. Because it partially melts, the crystal structure of the shell 101 is influenced by the crystal structure of the core 102, and the crystal structures of the shell 101 and the core 102 are substantially identical. The shell 101 thus formed stabilizes the crystal structure of the surface and bulk of the positive electrode active material particles 100. Therefore, changes in the crystal structure and / or oxygen release during charging of the positive electrode active material particles 100 can be effectively suppressed.

[0158] Note that the optimal heating temperature and heating time may vary depending on the particle size of the composite oxide 902.

[0159] Through the above process, positive electrode active material particles 100 can be produced (step S34).

[0160] [Manufacturing Method 2] In manufacturing method 1, Li x M 2-xA composite oxide represented by O2 was synthesized and then the additive element was added and heated, but the method for producing positive electrode active material particles of one embodiment of the present invention is not limited thereto. The additive element may be added at another timing, or may be added multiple times. The timing may be changed depending on the element. In Production Method 2, an example in which the additive element is added at a timing different from that in Production Method 1 will be described with reference to FIG. 3(B).

[0161] In Production Method 2 shown in FIG. 3(B), Li x M 2-x The additive element is added in the step of producing a composite oxide represented by O2 (M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti and Ru, 1<x<2). That is, in step S11, the additive element source is mixed together with the lithium source and the M source, and the mixture is heated for synthesis. Even in the case of such a production process, the shell 101 can contain a large amount of the additive element depending on the additive element and the heating conditions. For example, Li x M 2-x By using an additive element having a low solid solubility limit in the composite oxide represented by O2, the shell 101 containing a large amount of the additive element can be formed.

[0162] Except for the timing of adding the additive element, reference can be made to Production Method 1 and FIG. 3(A).

[0163] [Production Method 1-1] Next, Production Method 1-1, which is a more specific example of Production Method 1, will be described with reference to FIG. 4. In this production method, manganese and nickel are used as the transition metal M, and magnesium and fluorine are used as the additive elements.

[0164] First, as step S11 in FIG. 4, a lithium (Li) source, a manganese (Mn) source, and a nickel (Ni) source are prepared. As the lithium source, for example, lithium carbonate (Li2CO3) can be used. As the manganese source, for example, manganese carbonate (MnCO3) can be used. As the nickel source, for example, nickel carbonate (NiCO3) can be used.

[0165] Next, in step S12, a lithium source, a manganese source, and a nickel source are mixed to prepare a first mixture 901 (step S13). In this production method, a ball mill is used for the mixing, and the mixing is performed while cooling. Zirconia balls with a diameter of 3 mm are used as the media of the ball mill.

[0166] Next, in step S14, the first mixture 901 prepared above is heated. In this production method, the heating is performed while flowing dry air. The heating temperature can be 850°C or higher and lower than 950°C, typically 900°C. The heating time can be 2 hours or more and 20 hours or less, typically 10 hours. To distinguish it from other steps, the heating in step S14 may be referred to as first heating.

[0167] Next, in the case where the mixture is divided into a plurality of containers and heated in step S14, mixing is performed in step S15. It is preferable to employ a bead mill, a ball mill, a mortar, a mix rotor, and / or a mixer for the mixing.

[0168] Through the above steps, Li x M 2-x A composite oxide 902 represented by O2 is obtained (step S16).

[0169] Next, in step S21, a magnesium source and a fluorine source are prepared. In this production method, magnesium fluoride and lithium fluoride are used as the magnesium source and the fluorine source. Magnesium fluoride and lithium fluoride are a combination that easily turns into a liquid at a relatively low eutectic point around 742°C. Therefore, it is suitable as a flux that needs to function at a temperature not higher than the decomposition temperature of the composite oxide.

[0170] Next, in step S22, the magnesium source and fluorine source are ground and mixed. The method of ground and mixed is not particularly limited, but in this preparation method, a ball mill is used and the mixing and ground wet. Zirconia balls with a diameter of 1 mm are used as the media for the ball mill. Next, if necessary, the mixture media can be removed by sieving and the solvent can be dried.

[0171] The above process yields the source of added elements (step S23).

[0172] Next, in step S31, the composite oxide 902 and the additive element source are mixed to prepare a second mixture 903 (step S32). The mixing can be described in step S12.

[0173] Next, in step S33, the second mixture 903 is heated. In this manufacturing method, heating is performed while flowing oxygen through it. To distinguish it from other steps, the heating in step S33 is sometimes referred to as the second heating.

[0174] Through the above steps, positive electrode active material particles 100 can be produced (step S34). In this production method, production method 1 and Figure 3(A) can be referred to as appropriate.

[0175] This embodiment can be appropriately combined with the contents of other embodiments.

[0176] (Embodiment 3) This embodiment describes the configuration of a lithium-ion secondary battery.

[0177] [Positive electrode] The positive electrode comprises a positive electrode active material layer and a positive electrode current collector. The positive electrode active material layer contains positive electrode active material particles and may further contain at least one of a conductive additive and a binder. The positive electrode active material particles can be those described in the previous embodiment.

[0178] Alternatively, the positive electrode active material particles described in the previous embodiment may be mixed with other positive electrode active material particles and used together.

[0179] Other positive electrode active material particles include composite oxides having olivine-type crystal structures, layered rock salt-type crystal structures, or spinel-type crystal structures. Examples include compounds such as LiFePO4, LiFeO2, LiNiO2, LiMn2O4, V2O5, Cr2O5, and MnO2.

[0180] Figure 5(A) shows an example of a schematic diagram of the cross-section of the positive electrode.

[0181] The current collector 550 can be made of, for example, metal foil. The positive electrode can be formed by applying a slurry to the metal foil and drying it. Pressing may be applied after drying. The positive electrode is formed by forming an active material layer on the current collector 550. Although not shown in the figures, it is preferable to provide a conductive carbon coating layer between the active material and the current collector 550. Providing a conductive carbon coating layer can reduce the interfacial resistance between the aluminum foil and the active material, as well as the variation in that resistance.

[0182] A slurry is a liquid material used to form an active material layer on the current collector 550, and it contains an active material, a binder, and a solvent, preferably further mixed with a conductive additive. The slurry is also sometimes called an electrode slurry or an active material slurry. When forming a positive electrode active material layer, a positive electrode slurry is used, and when forming a negative electrode active material layer, it is sometimes called a negative electrode slurry.

[0183] The positive electrode active material particles 561 have the function of taking in and / or releasing lithium ions during charging and discharging. In one embodiment of the present invention, the positive electrode active material particles 561 can be made of a material that does not degrade much during charging and discharging, even at high charging voltages.

[0184] The positive electrode active material particles 561 used in one aspect of the present invention can be any material that exhibits little degradation during charging and discharging, even at high charging voltages, and those described in Embodiment 1 can be used. Furthermore, the positive electrode active material particles 561 can be made from two or more materials with different particle sizes, as long as they exhibit little degradation during charging and discharging, even at high charging voltages.

[0185] Conductive additives, also called conductivity imparters or conductive materials, can be made of carbon. By attaching a conductive additive between multiple active materials, the multiple active materials are electrically connected to each other, increasing conductivity. In this specification, "attachment" does not only refer to physical contact between the active materials and the conductive additive, but also includes cases where covalent bonding occurs, bonding occurs due to van der Waals forces, the conductive additive covers a portion of the surface of the active materials, the conductive additive fits into surface irregularities of the active materials, or where they are electrically connected even without physical contact.

[0186] Specific examples of carbon materials that can be used as conductive additives include carbon black (furnace black, acetylene black, graphite, etc.).

[0187] Figure 5(A) illustrates carbon black 553 as a conductive additive.

[0188] As the positive electrode of a lithium-ion secondary battery, a binder (resin) may be mixed to fix the current collector 550, such as metal foil, and the active material. The binder is also called a binding agent. The binder is a polymer material, and if a large amount of binder is included, the proportion of active material in the positive electrode decreases, reducing the discharge capacity of the lithium-ion secondary battery. Therefore, it is preferable to mix in the minimum amount of binder. In Figure 5(A), the areas not filled with positive electrode active material particles 561, the second active material 562, and carbon black 553 represent voids or binder.

[0189] Note that while Figure 5(A) shows an example where the positive electrode active material particles 561 are spherical, the figure is not particularly limited. For example, the cross-sectional shape of the positive electrode active material particles 561 may be elliptical, rectangular, trapezoidal, conical, a polygon with rounded corners, or asymmetrical. For example, Figure 5(B) shows an example where the positive electrode active material particles 561 have a polygonal shape with rounded corners.

[0190] Furthermore, in the positive electrode shown in Figure 5(B), graphene 554 is used as the carbon material used as a conductive additive. Figure 5(B) shows a positive electrode active material layer formed on the current collector 550, comprising positive electrode active material particles 561, graphene 554, and carbon black 553.

[0191] In the step of mixing graphene 554 and carbon black 553 to obtain an electrode slurry, it is preferable that the weight of the carbon black to be mixed be 1.5 times or more and 20 times or less the weight of the graphene, preferably 2 times or more and 9.5 times or less.

[0192] Furthermore, when the mixture of graphene 554 and carbon black 553 is within the above range, the dispersion stability of carbon black 553 is excellent during slurry preparation, and aggregation is less likely to occur. Also, when the mixture of graphene 554 and carbon black 553 is within the above range, a higher electrode density can be achieved compared to a positive electrode using only carbon black 553 as a conductive additive. By increasing the electrode density, the volume per unit weight can be increased. Specifically, the density of the positive electrode active material layer measured by gravimetric measurement can be 3.5 g / cc or higher.

[0193] Furthermore, although the electrode density is lower compared to positive electrodes using only graphene as a conductive additive, rapid charging can be achieved by using the above-mentioned range for the mixture of the first carbon material (graphene) and the second carbon material (acetylene black). For this reason, it is particularly effective when used as a lithium-ion secondary battery for automobiles.

[0194] Figure 5(C) illustrates an example of a cathode using carbon fiber 555 instead of graphene. Figure 5(C) shows a different example from Figure 5(B). Using carbon fiber 555 prevents aggregation of carbon black 553 and improves dispersibility.

[0195] In Figure 5(C), the areas not filled with positive electrode active material particles 561, carbon fibers 555, and carbon black 553 represent voids or binders.

[0196] Furthermore, Figure 5(D) illustrates an example of another cathode. Figure 5(D) shows an example in which carbon fiber 555 is used in addition to graphene 554. Using both graphene 554 and carbon fiber 555 can prevent aggregation of carbon black such as carbon black 553 and further improve dispersibility.

[0197] In Figure 5(D), the areas not filled with positive electrode active material particles 561, carbon fibers 555, graphene 554, and carbon black 553 represent voids or binders.

[0198] A lithium-ion secondary battery can be manufactured by using one of the positive electrodes shown in Figures 5(A) to 5(D), placing a separator on top of the positive electrode, and placing the resulting laminate on top of the separator, then placing it in a container (such as an outer casing or metal can), and filling the container with a liquid electrolyte.

[0199] <Binder> Preferably, the binder used is a rubber material such as styrene-butadiene rubber (SBR), styrene-isoprene-styrene rubber, acrylonitrile-butadiene rubber, butadiene rubber, or ethylene-propylene-diene copolymer. Fluororubber can also be used as a binder. The above rubber material can be dispersed in a dispersion medium and used. For example, one or more of the following can be used as the dispersion medium: water, N-methylpyrrolidone (NMP), methanol, ethanol, acetone, tetrahydrofuran (THF), dimethylformamide (DMF), and dimethyl sulfoxide (DMSO).

[0200] Furthermore, a water-soluble polymer can be used as a binder. Examples of water-soluble polymers include polysaccharides. Examples of polysaccharides include cellulose derivatives such as carboxymethylcellulose (CMC), methylcellulose, ethylcellulose, hydroxypropylcellulose, diacetylcellulose, and regenerated cellulose, or starch. It is also preferable to use these water-soluble polymers in combination with the aforementioned rubber material.

[0201] Alternatively, materials such as polystyrene, methyl polyacrylate, polymethyl methacrylate (PMMA), sodium polyacrylate, polyvinyl alcohol (PVA), polyethylene oxide (PEO), polypropylene oxide, polyimide, polyvinyl chloride, polytetrafluoroethylene, polyethylene, polypropylene, polyisobutylene, polyethylene terephthalate, nylon, polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), ethylene propylene diene polymer, polyvinyl acetate, and nitrocellulose may be used as binders.

[0202] You may use a combination of several of the binders mentioned above.

[0203] When a binder covers or is in contact with the surface of the active material, it is expected to act as a passivation film, suppressing the decomposition of the electrolyte. Here, a "passivation film" is a film that does not conduct electricity, or has extremely low electrical conductivity. For example, when a passivation film is formed on the surface of the active material, the decomposition of the electrolyte can be suppressed at the battery reaction potential. Furthermore, it is even more desirable for the passivation film to suppress electrical conductivity while still allowing lithium ions to conduct.

[0204] <Positive electrode current collector> As the current collector, highly conductive materials such as metals like aluminum, stainless steel, gold, platinum, titanium, and their alloys can be used. Furthermore, it is preferable that the material used for the positive electrode current collector does not dissolve at the positive electrode potential. Aluminum alloys with added elements that improve heat resistance, such as silicon, titanium, neodymium, scandium, and molybdenum, can also be used. Alternatively, the current collector may be formed from a metallic element that reacts with silicon to form a silicide. Examples of metallic elements that react with silicon to form a silicide include zirconium, titanium, hafnium, vanadium, niobium, tantalum, chromium, molybdenum, tungsten, cobalt, and nickel. The current collector can be in various shapes, such as foil, plate, sheet, mesh, perforated metal, or expanded metal. The current collector should preferably have a thickness of 5 μm to 30 μm.

[0205] [Negative electrode] The negative electrode comprises a negative electrode active material layer and a negative electrode current collector. The negative electrode active material layer may also contain a negative electrode active material, a conductive additive, and a binder.

[0206] <Negative electrode active material> For example, alloy materials and / or carbon materials can be used as the negative electrode active material.

[0207] The carbon material used for the negative electrode active material may be one or more selected from graphite, easily graphitizable carbon (soft carbon), difficult-to-graphitize carbon (hard carbon), carbon fibers (carbon nanotubes), graphene, carbon black, etc.

[0208] Graphite can be artificial graphite or natural graphite. Examples of artificial graphite include mesocarbon microbeads (MCMB), coke-based artificial graphite, and pitch-based artificial graphite. Spheroidal graphite, which has a spherical shape, can be used as the artificial graphite. For example, MCMB may have a spherical shape and is therefore preferable. Furthermore, it is relatively easy to reduce the surface area of ​​MCMB, which may also be preferable. Examples of natural graphite include flake graphite and spheroidized natural graphite.

[0209] When lithium ions are inserted into graphite (during the formation of lithium-graphite intercalation compounds), graphite exhibits a potential as low as that of lithium metal (0.05V to 0.3V vs. Li / Li). + This allows lithium-ion secondary batteries using graphite to exhibit a high operating voltage. Furthermore, graphite is preferable because it has advantages such as a relatively high capacity per unit volume, relatively small volume expansion, low cost, and higher safety compared to lithium metal.

[0210] Furthermore, for the negative electrode active material, an element capable of undergoing a charge-discharge reaction via an alloying-dealloying reaction with lithium can be used. For example, one or two or more materials selected from silicon, tin, gallium, aluminum, germanium, lead, antimony, bismuth, silver, zinc, cadmium, indium and the like can be used. Such elements have a larger capacity than carbon, and in particular, silicon has a high theoretical capacity of 4200 mAh / g. Moreover, compounds containing these elements may also be used. Examples include titanium silicide, titanium silicon oxide, SiO, Mg₂Si, Mg₂Ge, SnO, SnO₂, Mg₂Sn, SnS₂, V₂Sn₃, FeSn₂, CoSn₂, Ni₃Sn₂, Cu₆Sn₅, Ag₃Sn, Ag₃Sb, Ni₂MnSb, CeSb₃, LaSn₃, La₃Co₂Sn₇, CoSb₃, InSb, SbSn and the like. Here, an element capable of undergoing a charge-discharge reaction via an alloying-dealloying reaction with lithium, a compound containing the element, and the like may be referred to as an alloy-based material.

[0211] In this specification and the like, "SiO" refers to, for example, silicon monoxide. Alternatively, SiO can also be expressed as SiO x . Here, x preferably has a value of 1 or a value in the vicinity of 1. For example, x is preferably 0.2 or more and 1.5 or less, and more preferably 0.3 or more and 1.2 or less.

[0212] Furthermore, as the negative electrode active material, one or two or more oxides selected from titanium dioxide (TiO₂), lithium titanium oxide (Li₄Ti₅O 12 ), a lithium-graphite intercalation compound (Li x C₆), niobium pentoxide (Nb₂O₅), tungsten dioxide (WO₂), molybdenum dioxide (MoO₂) and the like can be used.

[0213] Furthermore, as the negative electrode active material, a lithium-transition metal nitride having a Li₃N-type structure, Li 3-x M x N (M=Co, Ni, Cu) can be used. For example, Li 2.6 Co 0.4 N has a large discharge capacity (900 mAh / g, 1890 mAh / cm3 ) indicates a preference.

[0214] When lithium and transition metal nitrides are used, lithium ions are contained in the negative electrode active material, making it preferable to combine them with materials that do not contain lithium ions, such as V2O5 and Cr3O8, as positive electrode active material particles. Even when using materials containing lithium ions as positive electrode active material particles, lithium and transition metal nitrides can be used as the negative electrode active material by removing the lithium ions contained in the positive electrode active material particles beforehand.

[0215] Furthermore, materials that undergo a conversion reaction can also be used as the negative electrode active material. For example, transition metal oxides that do not form alloys with lithium, such as cobalt oxide (CoO), nickel oxide (NiO), and iron oxide (FeO), may be used as the negative electrode active material. Other materials that undergo a conversion reaction include oxides such as Fe2O3, CuO, Cu2O, RuO2, Cr2O3, and CoS 0.89 This can also occur with sulfides such as NiS and CuS, nitrides such as Zn3N2, Cu3N, and Ge3N4, phosphides such as NiP2, FeP2, and CoP3, and fluorides such as FeF3 and BiF3.

[0216] Furthermore, multiple negative electrode active materials may be used in combination; for example, a negative electrode active material mixed with graphite and silicon particles may be used. Silicon particles refer to silicon powder used as a material for the negative electrode active material of a lithium-ion secondary battery, and the average particle size of the particle size distribution, i.e., the average particle diameter, is around 100 nm, and are sometimes called nanosilicon particles. It is preferable to grind the silicon raw material and adjust the particle size to a uniform particle size. The silicon particles may contain at least one of silicon, silicon oxide, or silicon alloy. While laser diffraction particle size distribution measurement is typically used to measure particle size, the method is not limited to laser diffraction particle size distribution measurement, and the major axis of the particle cross-section may be measured by analysis such as SEM (scanning electron microscope) or TEM (transmission electron microscope).

[0217] Furthermore, the same materials as those used for the conductive additive and binder in the positive electrode active material layer can be used for the conductive additive and binder in the negative electrode active material layer.

[0218] <Negative electrode current collector> In addition to the same materials as the positive electrode current collector, copper and other materials can also be used for the negative electrode current collector. It is preferable to use a material for the negative electrode current collector that does not alloy with carrier ions such as lithium.

[0219] [Electrolyte] The electrolyte contains an organic solvent, but the organic solvent is not limited to being a liquid at room temperature, for example, 25°C; it may also be a solid or semi-solid at room temperature. While it is preferable that the organic solvent be liquid over a wide temperature range including below freezing and high temperatures, it is not limited to this. The organic solvent may be liquid, solid, or semi-solid over a wide temperature range including below freezing and high temperatures.

[0220] As the organic solvent, aprotic organic solvents are preferred, such as ethylene carbonate (EC), propylene carbonate (PC), butylene carbonate, chloroethylene carbonate, vinylene carbonate, γ-butyrolactone, γ-valerolactone, dimethyl carbonate (DMC), diethyl carbonate (DEC), ethyl methyl carbonate (EMC), 1,3-propanesultone (PS), fluoroethylene carbonate (FEC), and methyl 3,3,3-tri One of the following can be used, or two or more of these, in any combination and ratio: fluoropropionate (MTFP), methyl formate, methyl acetate, ethyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, 1,3-dioxane, 1,4-dioxane, dimethoxyethane (DME), dimethyl sulfoxide, diethyl ether, methyl diglyme, acetonitrile, benzonitrile, tetrahydrofuran, sulfolane, sultone, etc.

[0221] The above organic solvent may contain additives. These additives can suppress the reactive decomposition of the electrolyte that may occur on the positive or negative electrode surface when the secondary battery is operated at high voltage and / or high temperature. Examples of suitable additives include vinylene carbonate (VC), propane sultone (PS), tert-butylbenzene (TBB), fluoroethylene carbonate (FEC), and lithium bis(oxalate) borate (LiBOB). LiBOB is particularly preferred because it readily forms a good film. VC or FEC are preferred because they form a good film on the negative electrode during aging or initial charging of the secondary battery, improving its cycle characteristics.

[0222] Because PS has the same highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO) levels as EC and DEC, it is less susceptible to oxidation and reduction even at high cutoff voltages, and when it decomposes on the surface of the positive electrode active material particles, it tends to form polymers. Therefore, it has the advantage of having a low possibility of gasification as small molecular weight decomposition products. For this reason, the electrolyte preferably contains 0.1 wt% to 10 wt% PS, and more preferably 0.25 wt% to 7.5 wt% PS.

[0223] FEC is a cyclic carbonate with a high dielectric constant, and when used in organic solvents, it promotes the dissociation of lithium salts. On the other hand, FEC has electron-withdrawing substituents, so desolvation with lithium ions proceeds more easily than with EC. Specifically, the solvation energy of lithium ions is lower for FEC than for EC, which does not have electron-withdrawing substituents. Therefore, lithium ions are more easily released from the surface of the positive electrode active material particles and the negative electrode active material, which can lower the internal resistance of the secondary battery. Furthermore, because FEC has a deep HOMO level, it is less susceptible to oxidation, improving oxidation resistance. However, the high viscosity of FEC is a concern. Therefore, it is preferable to use a mixed organic solvent containing not only FEC but also MTFP as the electrolyte. MTFP is a type of chain carbonate and can lower the viscosity of the electrolyte, or maintain the viscosity at room temperature (typically 25°C) even at low temperatures (typically 0°C). Furthermore, although MTFP has a lower solvation energy than methyl propionate (abbreviated as "MP") which does not have electron-withdrawing substituents, it may still generate solvation with lithium ions when used in an electrolyte. When using a mixed organic solvent containing both FEC and MTFP, the volume ratio is preferably y is 2 to 20, and more preferably 4 to 9, where FEC:MTFP = 1:y.

[0224] The organic solvent described above is preferably highly purified, with a low content of particulate matter or molecules other than the constituent molecules of the organic solvent (hereinafter also simply referred to as "impurities," which include oxygen (O2), water (H2O), or moisture). It is also preferable that reaction by-products during synthesis are suppressed through appropriate purification. Specifically, the impurity content of the electrolyte should be 100 ppm or less, preferably 50 ppm or less, and more preferably less than 10 ppm. The concentration of moisture among the impurities can be detected by Karl Fischer titration.

[0225] Furthermore, it is preferable that the above-mentioned organic solvent shows virtually no peaks attributable to impurities when measured by NMR or other methods. "Very virtually undetectable" means that the ratio of the integrated area of ​​the peaks attributable to impurities to the integrated area of ​​the peaks attributable to the main component (simply called the integration ratio) is 0.005 or less, preferably 0.002 or less. The instrument used for NMR measurement is not particularly limited, but for example, Bruker's "AVANCE III 400" can be used. Also, in 1H-NMR measurement, the central peak among the five peaks of acetonitrile derived from acetonitrile-d3 used as the solvent can be set to 1.94 ppm.

[0226] For example, in the case of MTFP, when 1H-NMR is measured using acetonitrile-d3 solvent, it is known that four peaks occur with δ between 3.29 ppm and 3.43 ppm. However, if other peaks occur in the vicinity of this range, for example, if a peak occurs with δ between 3.24 ppm and 3.29 ppm, that peak is considered to be due to impurities. Therefore, if the ratio (integral ratio) of the peak area between 3.24 ppm and 3.29 ppm to the peak area between 3.29 ppm and 3.43 ppm is 0.005 or less, preferably 0.002 or less, it can be said that peaks due to impurities are almost not detectable.

[0227] Furthermore, by using one or more ionic liquids (room-temperature molten salts) that are flame-retardant and less volatile as the solvent for the electrolytic solution, even if the internal temperature of the power storage device rises due to internal short circuit, overcharging or the like, rupture, ignition and the like of the power storage device can be prevented. The ionic liquid is composed of a cation and an anion, and includes an organic cation and an anion. Examples of the organic cation used in the electrolytic solution include aliphatic onium cations such as quaternary ammonium cation, tertiary sulfonium cation, and quaternary phosphonium cation, and aromatic cations such as imidazolium cation and pyridinium cation. Further, examples of the anion used in the electrolytic solution include monovalent amide anions, monovalent methide anions, fluorosulfonate anions, perfluoroalkylsulfonate anions, tetrafluoroborate anions, perfluoroalkylborate anions, hexafluorophosphate anions, or perfluoroalkylphosphate anions and the like.

[0228] Furthermore, examples of the electrolyte dissolved in the above solvent include LiPF6, LiClO4, LiAsF6, LiBF4, LiAlCl4, LiSCN, LiBr, LiI, Li2SO4, Li2B 10 Cl 10 , Li2B 12 Cl 12 , LiCF3SO3, LiC4F9SO3, LiC(CF3SO2)3, LiC(C2F5SO2)3, LiN(CF3SO2)2, LiN(C4F9SO2)(CF3SO2), LiN(C2F5SO2)2, lithium bis(oxalate)borate (Li(C2O4)2, LiBOB) and other lithium salts, one type thereof, or two or more types among them can be used in any optional combination and ratio.

[0229] As the electrolytic solution used in the power storage device, it is preferable to use a highly purified electrolytic solution with a low content of particulate dust or elements other than the constituent elements of the electrolytic solution (hereinafter also simply referred to as "impurities"). Specifically, the weight ratio of impurities to the electrolytic solution is preferably 1% or less, more preferably 0.1% or less, and even more preferably 0.01% or less.

[0230] Alternatively, a polymer gel electrolyte obtained by swelling a polymer with an electrolytic solution may be used.

[0231] By using the polymer gel electrolyte, safety against liquid leakage and the like is improved. In addition, the secondary battery can be made thinner and lighter.

[0232] As the polymer to be gelled, a silicone gel, an acrylic gel, an acrylonitrile gel, a polyethylene oxide-based gel, a polypropylene oxide-based gel, a fluorine-based polymer gel, or the like can be used. For example, a polymer having a polyalkylene oxide structure such as polyethylene oxide (PEO), PVDF, polyacrylonitrile, and copolymers containing these, and the like can be used. For example, PVDF-HFP, which is a copolymer of PVDF and hexafluoropropylene (HFP), can be used. In addition, the formed polymer may have a porous shape.

[0233] Further, as the electrolytic solution, a solid electrolyte containing an inorganic material such as a sulfide-based or oxide-based material, or a solid electrolyte containing a polymer material such as a PEO (polyethylene oxide)-based material can be used. When a solid electrolyte is used, installation of a separator or a spacer is not required. In addition, since the entire battery can be made solid, there is no risk of liquid leakage, and safety is dramatically improved.

[0234] [Separator] When a separator is placed between the positive and negative electrodes, the separator can be made of, for example, cellulose-containing fibers such as paper, nonwoven fabrics, glass fibers, ceramics, or synthetic fibers using nylon (polyamide), vinylon (polyvinyl alcohol-based fiber), polypropylene (PP), polyimide (PI), polyester, acrylic, polyolefin, or polyurethane. The porosity of the separator film thickness can be 35% to 90%, preferably 60% to 85%. A separator made of polypropylene can have a porosity of 35% to 45%. A separator made of polyimide can have a porosity of 75% to 85%. The film thickness of the separator is preferably 10 μm to 80 μm, and more preferably 20 μm to 60 μm. A separator made of polyimide can have a high porosity and can be made into a thick film (typically with a film thickness of 50 μm to 60 μm), which is preferable.

[0235] It is preferable that the separator be processed into a bag shape and positioned to enclose either the positive or negative electrode.

[0236] The separator may have a multilayer structure. For example, an organic material film such as polypropylene or polyethylene can be coated with a ceramic material, a fluorine material, a polyamide material, or a mixture thereof. Examples of ceramic materials include aluminum oxide particles and silicon oxide particles. Examples of fluorine materials include PVDF and polytetrafluoroethylene. Examples of polyamide materials include nylon and aramid (meta-aramid, para-aramid).

[0237] By using a multilayer separator, the safety of the lithium-ion secondary battery can be maintained even if the overall thickness of the separator is thin, thus increasing the capacity per unit volume of the lithium-ion secondary battery.

[0238] [Exterior] For the outer casing of a lithium-ion secondary battery, metal materials such as aluminum or resin materials can be used. Alternatively, a film-like outer casing can be used. As a film, for example, a three-layer film can be used, comprising a film made of materials such as polyethylene, polypropylene, polycarbonate, ionomer, or polyamide, on which a highly flexible metal thin film such as aluminum, stainless steel, copper, or nickel is provided, and further on which an insulating synthetic resin film such as a polyamide resin or polyester resin is provided as the outer surface of the outer casing.

[0239] This embodiment can be used in combination with other embodiments.

[0240] (Embodiment 4) This embodiment describes examples of lithium-ion secondary battery configurations.

[0241] [Laminated lithium-ion rechargeable battery] Examples of the configuration of a laminate-type lithium-ion secondary battery 500 are shown in Figures 6(A) and 6(B). Figures 6(A) and 6(B) are external views, and the lithium-ion secondary battery 500 has the electrolyte and separator (not shown in Figure 6) described in the above embodiment, a negative electrode 506, and a positive electrode 507. In the lithium-ion secondary battery 500, it is preferable that the negative electrode 506 has a larger area than the positive electrode 507. Furthermore, the lithium-ion secondary battery 500 has a negative electrode lead electrode 510 electrically connected to the negative electrode 506, and a positive electrode lead electrode 511 electrically connected to the positive electrode 507. The electrolyte, negative electrode 506, and positive electrode 507 are housed in an outer casing 509, and a part of the negative electrode lead electrode 510 and a part of the positive electrode lead electrode 511 protrude from the outer casing 509. A part of the outer circumference of the outer casing 509 has an adhesive region 508. Figure 6(A) shows an example configuration in which the negative lead electrode 510 and the positive lead electrode 511 protrude from the same side of the housing 509, and the adhesive region 508 is located at least on the side from which each lead electrode protrudes and on two sides adjacent to that side. Figure 6(B) shows an example configuration in which the side from which the negative lead electrode 510 protrudes from the housing 509 and the side from which the positive lead electrode 511 protrudes from the housing 509 are opposite each other, and the adhesive region 508 is located at least on the two sides from which each lead electrode protrudes and on the side sandwiched between those two sides. In Figures 6(A) and 6(B), the sides where the adhesive region 508 is not located preferably correspond to the sides where the housing 509 is folded.

[0242] By using the positive electrode active material particles of the present invention in a laminate-type lithium-ion secondary battery 500, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0243] [Coin-type lithium-ion rechargeable battery] An example of a coin-type lithium-ion secondary battery is described below. Figure 7(A) is an exploded perspective view of a coin-type (single-layer flat type) lithium-ion secondary battery, Figure 7(B) is an external view, and Figure 7(C) is a cross-sectional view thereof. Coin-type lithium-ion secondary batteries are mainly used in small electronic devices. In this specification, the term "coin-type lithium-ion secondary battery" includes button-type lithium-ion secondary batteries.

[0244] Figure 7(A) is a schematic diagram to show the overlapping of components (up / down relationship and positional relationship) for clarity. Therefore, Figure 7(A) and Figure 7(B) are not perfectly identical corresponding diagrams.

[0245] Figure 7(A) shows how the positive electrode 304, negative electrode 307, spacer 342, and washer 332 are stacked and sealed with the negative electrode can 302 and positive electrode can 301. Note that the electrolyte and separator described in the above embodiment are not shown in Figure 7(A). The spacer 342 and washer 332 are used to protect the inside or fix the position inside the can when the positive electrode can 301 and negative electrode can 302 are pressed together. The spacer 342 or washer 332 is made of stainless steel or an insulating material.

[0246] The positive electrode 304 is a laminated structure in which a positive electrode active material layer 306 is formed on a positive electrode current collector 305.

[0247] Figure 7(B) is a perspective view of the completed coin-type lithium-ion secondary battery 300.

[0248] The coin-type lithium-ion secondary battery 300 may have a positive electrode casing 301, which also serves as the positive electrode terminal, and a negative electrode casing 302, which also serves as the negative electrode terminal, insulated and sealed by a gasket 303 made of polypropylene or the like. The positive electrode 304 is formed by a positive electrode current collector 305 and a positive electrode active material layer 306 provided in contact with it. The negative electrode 307 is formed by a negative electrode current collector 308 and a negative electrode active material layer 309 provided in contact with it. The positive electrode casing 301 is electrically connected to the positive electrode 304, and the negative electrode casing 302 is electrically connected to the negative electrode 307.

[0249] It is preferable that the active material layer of each of the positive electrode 304 and the negative electrode 307 used in the coin-type lithium ion secondary battery 300 is formed only on one surface.

[0250] As shown in FIG. 7(C), with the positive electrode can 301 facing downward, the positive electrode 304, the negative electrode 307, and the negative electrode can 302 are stacked in this order, and the positive electrode can 301 and the negative electrode can 302 are crimped via the gasket 303 to manufacture the coin-shaped lithium ion secondary battery 300.

[0251] By using the positive electrode active material particles of the present invention in the coin-type lithium ion secondary battery 300, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0252] [Cylindrical Lithium Ion Secondary Battery] An example of a cylindrical lithium ion secondary battery will be described with reference to FIG. 8(A). As shown in FIG. 8(A), the cylindrical lithium ion secondary battery 616 has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (exterior can) 602 on the side surface and the bottom surface. The positive electrode cap 601 and the battery can (exterior can) 602 are insulated by a gasket (insulating packing) 610.

[0253] FIG. 8(B) is a diagram schematically showing a cross section of the cylindrical lithium ion secondary battery. The cylindrical lithium ion secondary battery shown in FIG. 8(B) has a positive electrode cap (battery lid) 601 on the top surface, and a battery can (exterior can) 602 on the side surface and the bottom surface. The positive electrode cap 601 and the battery can (exterior can) 602 are insulated by a gasket (insulating packing) 610.

[0254] Inside the hollow cylindrical battery can 602, a battery element is provided, in which a strip-shaped positive electrode 604 and a negative electrode 606 are wound with an electrolyte layer 605 in between. Although not shown, the battery element is wound around a central axis. The battery can 602 is closed at one end and open at the other. Inside the battery can 602, the battery element, in which the positive electrode, negative electrode, and separator are wound, is sandwiched between a pair of opposing insulating plates 608 and insulating plate 609. Furthermore, the inside of the battery can 602 in which the battery element is provided is filled with an electrolyte (not shown).

[0255] Since the positive and negative electrodes used in cylindrical storage batteries are wound, it is preferable to form the active material on both sides of the current collector. Figures 8(A) to 8(D) illustrate a lithium-ion secondary battery 616 in which the height of the cylinder is greater than the diameter of the cylinder, but the battery is not limited to this configuration. A lithium-ion secondary battery in which the diameter of the cylinder is greater than the height of the cylinder is also possible. Such a configuration allows for, for example, miniaturization of the lithium-ion secondary battery.

[0256] A positive electrode terminal (positive electrode current collector lead) 603 is connected to the positive electrode 604, and a negative electrode terminal (negative electrode current collector lead) 607 is connected to the negative electrode 606. Aluminum can be used for the positive electrode terminal 603, and copper or other metal materials can be used for the negative electrode terminal 607. The positive electrode terminal 603 is resistance-welded to the safety valve mechanism 613, and the negative electrode terminal 607 is resistance-welded to the bottom of the battery can 602. The safety valve mechanism 613 is electrically connected to the positive electrode cap 601 via a PTC element (Positive Temperature Coefficient) 611. The safety valve mechanism 613 disconnects the electrical connection between the positive electrode cap 601 and the positive electrode 604 when the internal pressure of the battery exceeds a predetermined threshold. The PTC element 611 is a thermal resistance element whose resistance increases when the temperature rises, limiting the current and preventing abnormal heat generation. Barium titanate (BaTiO3) based ceramic materials can be used for the PTC element.

[0257] Figure 8(C) shows an example of an energy storage system 615. The energy storage system 615 has multiple lithium-ion secondary batteries 616 and is sometimes called a battery pack. The positive electrode of each lithium-ion secondary battery is in contact with a conductor 624 separated by an insulator 625 and is electrically connected. The conductor 624 is electrically connected to the control circuit 620 via wiring 623. The negative electrode of each lithium-ion secondary battery is also electrically connected to the control circuit 620 via wiring 626. The control circuit 620 can be a protective circuit to prevent overcharging or over-discharging, etc.

[0258] Figure 8(D) shows an example of an energy storage system 615. The energy storage system 615 has multiple lithium-ion secondary batteries 616, which are sandwiched between conductive plates 628 and 614. The multiple lithium-ion secondary batteries 616 are electrically connected to the conductive plates 628 and 614 by wiring 627. The multiple lithium-ion secondary batteries 616 may be connected in parallel, in series, or connected in parallel and then in series. By configuring an energy storage system 615 with multiple lithium-ion secondary batteries 616, a large amount of power can be extracted.

[0259] Multiple lithium-ion secondary batteries 616 may be connected in parallel and then further connected in series.

[0260] A temperature control device may be provided between multiple lithium-ion secondary batteries 616. When a lithium-ion secondary battery 616 overheats, it can be cooled by the temperature control device, and when a lithium-ion secondary battery 616 becomes too cold, it can be heated by the temperature control device. This makes the performance of the energy storage system 615 less susceptible to the influence of ambient temperature.

[0261] Furthermore, in Figure 8(D), the energy storage system 615 is electrically connected to the control circuit 620 via wiring 621 and wiring 622. Wiring 621 is electrically connected to the positive electrodes of the multiple lithium-ion secondary batteries 616 via conductive plate 628, and wiring 622 is electrically connected to the negative electrodes of the multiple lithium-ion secondary batteries 616 via conductive plate 614.

[0262] By using the positive electrode active material particles of the present invention in a cylindrical lithium-ion secondary battery 616, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0263] [Other structural examples of lithium-ion secondary batteries] Examples of lithium-ion secondary battery structures are explained using Figures 9 and 10.

[0264] The lithium-ion secondary battery 913 shown in Figure 9(A) has a wound body 950 with terminals 951 and 952 inside a housing 930. The wound body 950 is impregnated with an electrolyte inside the housing 930. Terminal 952 is in contact with the housing 930, while terminal 951 is not in contact with the housing 930 due to the use of an insulating material or the like. In Figure 9(A), the housing 930 is shown separated for convenience, but in reality, the wound body 950 is covered by the housing 930, and terminals 951 and 952 extend outside the housing 930. The housing 930 can be made of a metal material (e.g., aluminum), a composite material of metal and resin, etc.

[0265] Furthermore, as shown in Figure 9(B), the housing 930 shown in Figure 9(A) may be formed from multiple materials. For example, in the lithium-ion secondary battery 913 shown in Figure 9(B), housing 930a and housing 930b are bonded together, and a winding body 950 is provided in the area surrounded by housing 930a and housing 930b.

[0266] An insulating material can be used for the housing 930a. In particular, by using a material such as organic resin on the surface where the antenna is formed, shielding of the electric field by the lithium-ion secondary battery 913 can be suppressed. If the shielding of the electric field by the housing 930a is small, the antenna may be placed inside the housing 930a. For the housing 930b, for example, a metal material can be used.

[0267] Furthermore, the structure of the wound body 950 is shown in Figure 9(C). The wound body 950 has a negative electrode 931, a positive electrode 932, and a separator 933. The wound body 950 is a wound body in which the negative electrode 931 and the positive electrode 932 are stacked on top of each other with the separator 933 in between, and the stacked sheets are wound up. Note that multiple stacks of the negative electrode 931, positive electrode 932, and separator 933 may be stacked.

[0268] Alternatively, the lithium-ion secondary battery 913 may have a wound body 950a as shown in Figures 10(A) to 10(C). The wound body 950a shown in Figure 10(A) has a negative electrode 931, a positive electrode 932, and a separator 933. The negative electrode 931 has a negative electrode active material layer 931a. The positive electrode 932 has a positive electrode active material layer 932a.

[0269] The separator 933 has a wider width than the negative electrode active material layer 931a and the positive electrode active material layer 932a, and is wound so as to overlap with the negative electrode active material layer 931a and the positive electrode active material layer 932a. Furthermore, it is preferable from a safety standpoint that the negative electrode active material layer 931a is wider than the positive electrode active material layer 932a. A wound body 950a of this shape is also preferable due to its good safety and productivity.

[0270] As shown in Figure 10(B), the negative electrode 931 is electrically connected to terminal 951. Terminal 951 is electrically connected to terminal 911a. The positive electrode 932 is electrically connected to terminal 952. Terminal 952 is electrically connected to terminal 911b.

[0271] As shown in Figure 10(C), the coiled body 950a is covered by the housing 930, forming a lithium-ion secondary battery 913. It is preferable to provide a safety valve, an overcurrent protection element, etc., in the housing 930. The safety valve is a valve that opens the inside of the housing 930 at a predetermined internal pressure in order to prevent the battery from rupturing.

[0272] As shown in Figure 10(B), the lithium-ion secondary battery 913 may have multiple windings 950a. By using multiple windings 950a, a lithium-ion secondary battery 913 with a larger charge and discharge capacity can be made. Other elements of the lithium-ion secondary battery 913 shown in Figures 10(A) and (B) can be referenced from the description of the lithium-ion secondary battery 913 shown in Figures 9(A) to 9(C).

[0273] By using the positive electrode active material particles of the present invention in a lithium-ion secondary battery 913 having a wound body, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0274] The contents of this embodiment can be appropriately combined with the contents of other embodiments.

[0275] (Embodiment 5) In this embodiment, an example of application to an electric vehicle (EV) is shown using Figure 11.

[0276] As shown in Figure 11(A), the electric vehicle is equipped with a first lithium-ion secondary battery 1301a and 1301b as the main drive lithium-ion secondary battery, and a second battery 1311 that supplies power to the inverter 1312 that starts the motor 1304. By using the positive electrode active material particles of the present invention in the first batteries 1301a and 1301b, it is possible to create a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics.

[0277] The second battery 1311 is also called the cranking battery (or starter battery). The second battery 1311 only needs to be able to output high power, and does not require a large capacity. Therefore, the capacity of the second battery 1311 is smaller than that of the first batteries 1301a and 1301b.

[0278] The internal structure of the first battery 1301a may be wound or stacked.

[0279] In this embodiment, an example is shown in which two first batteries 1301a and 1301b are connected in parallel, but three or more may be connected in parallel. Also, if the first battery 1301a can store sufficient power, the first battery 1301b may not be necessary. By configuring a battery pack having multiple lithium-ion secondary batteries, a large amount of power can be extracted. Multiple lithium-ion secondary batteries may be connected in parallel, in series, or connected in parallel and then in series. Multiple lithium-ion secondary batteries are also called a battery pack.

[0280] Furthermore, the lithium-ion secondary battery for use in vehicles has a service plug or circuit breaker that can cut off high voltage without using tools in order to cut off power from multiple lithium-ion secondary batteries, and this is provided in the first battery 1301a.

[0281] Furthermore, the power from the first batteries 1301a and 1301b is mainly used to rotate the motor 1304, but also supplies power to 42V onboard components (electric power steering 1307, heater 1308, defogger 1309, etc.) via the DC / DC circuit 1306. If a rear motor 1317 is located on the rear wheels, the first battery 1301a is used to rotate the rear motor 1317.

[0282] Furthermore, the second battery 1311 supplies power to 14V automotive components (audio system 1313, power windows 1314, lights 1315, etc.) via the DC / DC circuit 1310.

[0283] Furthermore, the first battery 1301a will be explained using Figure 11(B).

[0284] Figure 11(B) shows an example in which nine prismatic lithium-ion secondary batteries 1300 are arranged in a single battery pack 1415. In this example, nine prismatic lithium-ion secondary batteries 1300 are connected in series, with one electrode fixed by an insulating fixing part 1413 and the other electrode fixed by an insulating fixing part 1414. This embodiment shows an example of fixing with fixing parts 1413 and 1414, but it is also possible to house the batteries in a battery housing box (also called a casing). Since vehicles are expected to be subjected to vibrations or shaking from the outside (road surface, etc.), it is preferable to fix multiple lithium-ion secondary batteries with fixing parts 1413 and 1414 and a battery housing box. In addition, one electrode is electrically connected to the control circuit unit 1320 by wiring 1421. The other electrode is electrically connected to the control circuit unit 1320 by wiring 1422.

[0285] Furthermore, the control circuit unit 1320 may also use a memory circuit that includes a transistor made of an oxide semiconductor. A charging control circuit or battery control system having a memory circuit that includes a transistor made of an oxide semiconductor may be referred to as a BTOS (Battery operating system or Battery oxide semiconductor).

[0286] It is preferable to use a metal oxide that functions as an oxide semiconductor. For example, as the oxide, a metal oxide such as In-M2-Zn oxide (where element M2 is one or more selected from aluminum, gallium, yttrium, copper, vanadium, beryllium, boron, titanium, iron, nickel, germanium, zirconium, molybdenum, lanthanum, cerium, neodymium, hafnium, tantalum, tungsten, or magnesium) is preferable. In particular, the In-M2-Zn oxide that can be applied as the oxide is preferably CAAC-OS (C-Axis Aligned Crystal Oxide Semiconductor) or CAC-OS (Cloud-Aligned Composite Oxide Semiconductor). Alternatively, In-Ga oxide or In-Zn oxide may be used as the oxide. CAAC-OS is an oxide semiconductor having multiple crystalline regions, in which the c-axis of these crystalline regions is oriented in a specific direction. The specific direction refers to the thickness direction of the CAAC-OS film, the normal direction to the surface on which the CAAC-OS film is formed, or the normal direction to the surface of the CAAC-OS film. Furthermore, a crystalline region is a region in which the atomic arrangement has periodicity. If the atomic arrangement is considered as a lattice arrangement, then a crystalline region is also a region in which the lattice arrangement is aligned. In addition, CAAC-OS has regions in the ab-plane direction where multiple crystalline regions are connected, and these regions may have distortion. Distortion refers to the point in a region where multiple crystalline regions are connected where the orientation of the lattice arrangement changes between a region with an aligned lattice arrangement and another region with an aligned lattice arrangement. In other words, CAAC-OS is an oxide semiconductor that is c-axis oriented and does not have a clear orientation in the ab-plane direction.

[0287] Furthermore, since it can be used in low-temperature environments, it is preferable that the control circuit section 1320 uses a transistor made of oxide semiconductor. To simplify the process, the control circuit section 1320 may also be formed using a unipolar transistor. Transistors using oxide semiconductors in the semiconductor layer have an operating ambient temperature range of -40°C to 150°C, which is wider than that of single-crystal Si, and the characteristic change is smaller when the lithium-ion secondary battery is heated compared to single crystal. The off-current of a transistor using an oxide semiconductor is below the lower limit of measurement regardless of temperature, even at 150°C, but the off-current characteristics of a single-crystal Si transistor are highly temperature-dependent. For example, at 150°C, the off-current of a single-crystal Si transistor increases, and the current on / off ratio does not become sufficiently large. The control circuit section 1320 can improve safety.

[0288] The control circuit unit 1320, which uses a memory circuit including an oxide semiconductor transistor, can also function as an automatic control device for lithium-ion secondary batteries to address 10 causes of instability, such as micro-short circuits. Functions to eliminate the 10 causes of instability include overcharge prevention, overcurrent prevention, overheat control during charging, cell balancing in the battery pack, over-discharge prevention, remaining charge indicator, automatic control of charging voltage and current according to temperature, charging current control according to the degree of degradation, detection of abnormal behavior related to micro-short circuits, and prediction of abnormalities related to micro-short circuits. The control circuit unit 1320 has at least one of these functions. Furthermore, it is possible to miniaturize the automatic control device for lithium-ion secondary batteries.

[0289] Furthermore, a microshort refers to a tiny short circuit inside a lithium-ion secondary battery. One of the causes of microshorts is said to be that, due to multiple charge-discharge cycles, the uneven distribution of positive electrode active material particles causes localized current concentration in parts of the positive electrode and parts of the negative electrode, or that micro-short circuits occur due to the generation of by-reactants from side reactions.

[0290] Furthermore, in addition to detecting micro-shorts, the control circuit unit 1320 also detects the terminal voltage of the lithium-ion secondary battery and manages the charging and discharging state of the lithium-ion secondary battery. For example, to prevent overcharging, both the output transistor and the cutoff switch of the charging circuit can be turned off almost simultaneously.

[0291] Furthermore, an example of a block diagram of the battery pack 1415 shown in Figure 11(B) is shown in Figure 11(C).

[0292] The control circuit unit 1320 includes at least a switch to prevent overcharging, a switch unit 1324 including a switch to prevent over-discharging, a control circuit 1322 that controls the switch unit 1324, and a voltage measurement unit for the first battery 1301a. The control circuit unit 1320 has upper and lower voltage limits set for the lithium-ion secondary battery used, and limits the upper limit of external current and the upper limit of output current to the outside. Within the range between the lower voltage limit and the upper voltage limit of the lithium-ion secondary battery, it is within the voltage range for which use is recommended, and if it goes outside this range, the switch unit 1324 activates and functions as a protection circuit. The control circuit unit 1320 can also be called a protection circuit because it controls the switch unit 1324 to prevent over-discharge and overcharge. For example, if the control circuit 1322 detects a voltage that is likely to cause overcharging, it cuts off the current by turning off the switch unit 1324. Furthermore, a PTC element may be provided in the charge / discharge path to provide a function to cut off the current in response to the rise in temperature. Furthermore, the control circuit unit 1320 has an external terminal 1325 (+IN) and an external terminal 1326 (-IN).

[0293] The switch section 1324 can be constructed by combining an n-channel transistor and a p-channel transistor. The switch section 1324 is not limited to a switch having a Si transistor using single-crystal silicon, but can also be made of, for example, Ge (germanium), SiGe (silicon germanium), GaAs (gallium arsenide), GaAlAs (gallium aluminum arsenide), InP (indium phosphide), SiC (silicon carbide), ZnSe (zinc selenide), GaN (gallium nitride), GaOx The switch section 1324 may be formed using a power transistor having (gallium oxide; x is a real number greater than 0), etc. Furthermore, since memory elements using OS transistors can be freely arranged by stacking them on circuits using Si transistors, integration can be easily achieved. By stacking a control circuit section 1320 using OS transistors on the switch section 1324 and integrating them, it is possible to create a single chip, enabling miniaturization.

[0294] The first batteries 1301a and 1301b primarily supply power to 42V (high-voltage) onboard equipment, while the second battery 1311 supplies power to 14V (low-voltage) onboard equipment. Lead-acid batteries are often used for the second battery 1311 due to cost advantages. While using a lithium-ion secondary battery for the second battery 1311 offers the advantage of being maintenance-free, prolonged use, such as more than three years, may lead to malfunctions that were not detectable at the time of manufacture. In particular, if the second battery 1311, which starts the inverter, becomes inoperable, it may become impossible to start the motor even if the first batteries 1301a and 1301b have remaining capacity. To prevent this, if the second battery 1311 is a lead-acid battery, power is supplied from the first battery to the second battery to keep it constantly fully charged.

[0295] In this embodiment, an example is shown in which lithium-ion secondary batteries are used for both the first battery 1301a and the second battery 1311. However, the second battery 1311 may be a lead-acid battery, an all-solid-state battery, or an electric double-layer capacitor. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery described above, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0296] Furthermore, the regenerative energy generated by the rotation of the tire 1316 is sent to the motor 1304 via the gear 1305 and charged to the second battery 1311 via the control circuit unit 1321 from the motor controller 1303 and battery controller 1302. Alternatively, it is charged to the first battery 1301a via the control circuit unit 1320 from the battery controller 1302. Alternatively, it is charged to the first battery 1301b via the control circuit unit 1320 from the battery controller 1302. In order to efficiently charge the regenerative energy, it is desirable that the first batteries 1301a and 1301b are capable of rapid charging.

[0297] The battery controller 1302 can set the charging voltage and charging current of the first batteries 1301a and 1301b. The battery controller 1302 can set the charging conditions according to the charging characteristics of the lithium-ion secondary battery used and enable rapid charging.

[0298] Although not shown in the diagram, when connected to an external charger, the charger's outlet or connection cable is electrically connected to the battery controller 1302. Power supplied from the external charger is charged to the first batteries 1301a and 1301b via the battery controller 1302. In some cases, the charger may have a control circuit and may not use the functions of the battery controller 1302, but it is preferable to charge the first batteries 1301a and 1301b via the control circuit unit 1320 to prevent overcharging. In some cases, the connection cable or the charger's connection cable may also have a control circuit. The control circuit unit 1320 is sometimes called an ECU (Electronic Control Unit). The ECU is connected to a CAN (Controller Area Network) installed in the electric vehicle. CAN is one of the serial communication standards used as an in-vehicle LAN. The ECU also includes a microcomputer. The ECU also uses a CPU or GPU.

[0299] External chargers installed at charging stations and other locations include 100V outlets, 200V outlets, and 3-phase 200V with 50kW output. Additionally, it is possible to charge by receiving power from external charging equipment using contactless power supply methods.

[0300] Next, we will describe an example in which a lithium-ion secondary battery, which is one aspect of the present invention, is implemented in a vehicle, typically a transport vehicle.

[0301] Furthermore, equipping vehicles with lithium-ion secondary batteries can enable the realization of next-generation clean energy vehicles such as hybrid vehicles (HV), electric vehicles (EV), or plug-in hybrid vehicles (PHV). Lithium-ion secondary batteries can also be installed in agricultural machinery, motorized bicycles including electric-assist bicycles, motorcycles, electric wheelchairs, electric carts, small or large vessels, submarines, aircraft such as fixed-wing and rotary-wing aircraft, rockets, satellites, space probes, planetary probes, and spacecraft.

[0302] Figures 12(A) to 12(D) illustrate a transport vehicle using one embodiment of the present invention. The automobile 2001 shown in Figure 12(A) is an electric vehicle that uses an electric motor as a power source for driving. Alternatively, it is a hybrid vehicle that can appropriately select and use an electric motor and an engine as power sources for driving. When a lithium-ion secondary battery is installed in the vehicle, one or more examples of the lithium-ion secondary battery shown in the above embodiment are installed in one location. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery installed in the vehicle, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0303] The automobile 2001 shown in Figure 12(A) has a battery pack 2200, which has a battery module to which a plurality of lithium-ion secondary batteries are connected. Furthermore, it is preferable that the battery pack 2200 has a charge control device electrically connected to the battery module.

[0304] Furthermore, the automobile 2001 can be charged by receiving power from an external charging facility via a plug-in method or contactless power supply method, etc., for the lithium-ion secondary battery it possesses. When charging, the charging method and connector specifications may be carried out as appropriate using a prescribed method such as CHAdeMO (registered trademark) or Combo. External charging facilities can include charging stations installed in commercial facilities, household power supplies, etc. For example, the battery storage device mounted on the automobile 2001 can be charged by supplying power from an external source using plug-in technology. Charging can be performed by converting alternating current power to direct current power via a conversion device such as an AC / DC converter.

[0305] Although not shown in the diagram, the vehicle can also be charged by mounting a power receiving device on the vehicle and supplying power wirelessly from a ground-based power transmission device. In this wireless power supply method, charging can be performed not only when the vehicle is stopped but also while it is in motion by incorporating the power transmission device into the road or exterior wall. Furthermore, this wireless power supply method can be used to transmit and receive power between two vehicles. In addition, solar panels can be installed on the exterior of the vehicle to charge the lithium-ion secondary battery when the vehicle is stopped and when it is in motion. For such wireless power supply, an electromagnetic induction method or a magnetic field resonance method can be used.

[0306] Figure 12(B) shows a large transport vehicle 2002 equipped with an electrically controlled motor as an example of a transport vehicle. The battery module of the transport vehicle 2002 has a maximum voltage of 170V, achieved by connecting 48 cells in series, each consisting of four lithium-ion secondary batteries with a nominal voltage of 3.0V to 5.0V. Except for the number of lithium-ion secondary batteries in the battery pack 2201, it has the same functions as the battery pack shown in Figure 11(B), so the explanation is omitted. By using the positive electrode active material particles of the present invention in the lithium-ion secondary batteries of the battery pack 2201, it is possible to create a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics.

[0307] Figure 12(C) shows, as an example, a large transport vehicle 2003 equipped with an electrically controlled motor. The battery module of the transport vehicle 2003 can have a maximum voltage of 600V by connecting, for example, 100 or more lithium-ion secondary batteries with a nominal voltage of 3.0V to 5.0V in series. The battery pack 2202 of the transport vehicle 2003 has the same functions as the battery pack 1415 shown in Figure 11(B), except for differences in the number of cells connected in series or the number of cells constituting the battery module, so a detailed explanation is omitted. By using the positive electrode active material particles of the present invention in the lithium-ion secondary batteries of the battery module, it is possible to create a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics.

[0308] Figure 12(D) shows an example of an aircraft 2004 having a fuel-burning engine. The aircraft 2004 shown in Figure 12(D) has wheels for takeoff and landing, and can therefore be considered part of a transport vehicle. It has a battery pack 2203 which includes a battery module formed by connecting multiple lithium-ion secondary batteries and a charge control device.

[0309] The battery module for aircraft 2004 has a maximum voltage of 32V, for example, by connecting eight 4V lithium-ion secondary batteries in series. Aside from differences in the number of lithium-ion secondary batteries that make up the battery module of battery pack 2203, it has similar functions to the battery pack shown in Figure 11(B), so a detailed explanation is omitted.

[0310] The contents of this embodiment can be appropriately combined with the contents of other embodiments.

[0311] (Embodiment 6) This embodiment shows an example in which a lithium-ion secondary battery according to one aspect of the present invention is mounted on a vehicle such as a motorcycle or bicycle.

[0312] Figure 13(A) shows an example of an electric bicycle using a lithium-ion secondary battery according to one embodiment of the present invention. The lithium-ion secondary battery according to one embodiment of the present invention can be applied to the electric bicycle 8700 shown in Figure 13(A). The lithium-ion secondary battery according to one embodiment of the present invention may have a protection circuit.

[0313] The electric bicycle 8700 is equipped with a power storage device 8702. The power storage device 8702 can supply electricity to a motor that assists the rider. The power storage device 8702 is also portable, and Figure 13(B) shows it detached from the bicycle. The power storage device 8702 also contains multiple lithium-ion secondary batteries 8701 according to one embodiment of the present invention, and the remaining battery level and other information can be displayed on the display unit 8703. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery 8701, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0314] Furthermore, the energy storage device 8702 has a control circuit 8704 capable of controlling the charging of the lithium-ion secondary battery or detecting abnormalities. The control circuit 8704 is electrically connected to the positive and negative electrodes of the lithium-ion secondary battery 8701. This can greatly contribute to eliminating accidents such as fires caused by lithium-ion secondary batteries.

[0315] Figure 13(C) shows an example of a motorcycle using a lithium-ion secondary battery according to one embodiment of the present invention. The scooter 8600 shown in Figure 13(C) is equipped with a power storage device 8602, side mirrors 8601, and turn signals 8603. The power storage device 8602 can supply electricity to the turn signals 8603. By using the positive electrode active material particles of the present invention in a lithium-ion secondary battery, it is possible to create a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics.

[0316] The scooter 8600 shown in Figure 13(C) can accommodate the power storage device 8602 in the under-seat storage compartment 8604. The power storage device 8602 can be stored in the under-seat storage compartment 8604 even if the under-seat storage compartment 8604 is small.

[0317] The contents of this embodiment can be appropriately combined with the contents of other embodiments.

[0318] (Embodiment 7) This embodiment describes an example of mounting a lithium-ion secondary battery, which is one aspect of the present invention, in an electronic device. Examples of electronic devices that mount a lithium-ion secondary battery include television equipment (also called televisions or television receivers), monitors for computers, digital cameras, digital video cameras, digital photo frames, mobile phones (also called mobile phones or mobile phone devices), portable game consoles, personal information terminals, sound playback devices, and large game machines such as pachinko machines. Personal information terminals include notebook personal computers, tablet terminals, e-book readers, and mobile phones.

[0319] Figure 14(A) shows an example of a mobile phone. The mobile phone 2100 includes a display unit 2102 built into the housing 2101, as well as operation buttons 2103, an external connection port 2104, a speaker 2105, a microphone 2106, and the like. The mobile phone 2100 has a lithium-ion secondary battery 2107. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery, it is possible to create a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics.

[0320] The mobile phone 2100 can run various applications such as making phone calls, sending emails, reading and creating documents, playing music, communicating on the internet, and playing computer games.

[0321] The operation button 2103 can be assigned various functions, including time setting, power on / off operation, wireless communication on / off operation, silent mode activation / deactivation, and power saving mode activation / deactivation. For example, the function of the operation button 2103 can be freely configured by the operating system built into the mobile phone 2100.

[0322] Furthermore, the 2100 mobile phone is capable of performing standardized short-range wireless communication. For example, it can communicate with a wireless headset to enable hands-free calling.

[0323] Furthermore, the mobile phone 2100 is equipped with an external connection port 2104, which allows for direct data exchange with other information terminals via a connector. It can also be charged via the external connection port 2104. Note that charging may also be performed wirelessly without using the external connection port 2104.

[0324] The mobile phone 2100 preferably has sensors. For example, it is preferable that the sensor includes a human body sensor such as a fingerprint sensor, pulse sensor, or body temperature sensor, as well as a touch sensor, pressure sensor, acceleration sensor, etc.

[0325] Figure 14(B) shows an unmanned aerial vehicle 2300 having multiple rotors 2302. The unmanned aerial vehicle 2300 is sometimes called a drone. The unmanned aerial vehicle 2300 has a lithium-ion secondary battery 2301, a camera 2303, and an antenna (not shown), which are embodiments of the present invention. The unmanned aerial vehicle 2300 can be remotely controlled via the antenna. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0326] Figure 14(C) shows an example of a robot. The robot 6400 shown in Figure 14(C) is equipped with a lithium-ion secondary battery 6409, an illuminance sensor 6401, a microphone 6402, an upper camera 6403, a speaker 6404, a display unit 6405, a lower camera 6406, an obstacle sensor 6407, a movement mechanism 6408, a computing device, and the like.

[0327] Microphone 6402 has the function of detecting the user's voice and ambient sounds. Speaker 6404 has the function of emitting sound. Robot 6400 can communicate with the user using microphone 6402 and speaker 6404.

[0328] The display unit 6405 has the function of displaying various types of information. The robot 6400 can display the user's desired information on the display unit 6405. The display unit 6405 may be equipped with a touch panel. The display unit 6405 may also be a detachable information terminal, and by installing it in a fixed position on the robot 6400, charging and data transfer can be enabled.

[0329] The upper camera 6403 and the lower camera 6406 have the function of imaging the area around the robot 6400. In addition, the obstacle sensor 6407 can detect the presence or absence of obstacles in the direction of travel when the robot 6400 moves forward using the movement mechanism 6408. The robot 6400 can recognize its surrounding environment and move safely using the upper camera 6403, the lower camera 6406 and the obstacle sensor 6407.

[0330] The robot 6400 is equipped with a lithium-ion secondary battery 6409 according to one aspect of the present invention and a semiconductor device or electronic components in its internal region. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0331] Figure 14(D) shows an example of a cleaning robot. The cleaning robot 6300 has a display unit 6302 located on the top surface of the housing 6301, multiple cameras 6303 located on the sides, a brush 6304, operation buttons 6305, a lithium-ion secondary battery 6306, and various sensors. Although not shown, the cleaning robot 6300 is equipped with wheels, a suction port, etc. The cleaning robot 6300 is self-propelled, can detect dirt 6310, and can suck up the dirt from a suction port located on the bottom surface.

[0332] For example, the cleaning robot 6300 can analyze images captured by the camera 6303 to determine the presence or absence of obstacles such as walls, furniture, or steps. Furthermore, if the image analysis detects an object that might become entangled in the brush 6304, such as wiring, the rotation of the brush 6304 can be stopped. The cleaning robot 6300 is equipped with a lithium-ion secondary battery 6306 according to one aspect of the present invention and a semiconductor device or electronic components within its internal region. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be obtained.

[0333] This embodiment can be implemented in appropriate combination with other embodiments.

[0334] (Embodiment 8) This embodiment describes an example of implementing a lithium-ion secondary battery, which is one aspect of the present invention, in space equipment.

[0335] Figure 15(A) shows satellite 6800 as an example of space equipment. Satellite 6800 consists of the airframe 6801, solar panels 6802, an antenna 6803, and a lithium-ion secondary battery 6805. The solar panels are sometimes called solar cell modules.

[0336] When sunlight shines on the solar panel 6802, the power necessary for the satellite 6800 to operate is generated. However, in situations where, for example, sunlight does not shine on the solar panel, or when the amount of sunlight shining on the solar panel is low, the amount of power generated will decrease. Therefore, there is a possibility that the power necessary for the satellite 6800 to operate will not be generated. To operate the satellite 6800 even under conditions where the amount of power generated is low, it is advisable to equip the satellite 6800 with a lithium-ion secondary battery 6805. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery, it is possible to create a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics.

[0337] The satellite 6800 can generate a signal. This signal is transmitted via antenna 6803, and can be received by, for example, a receiver on the ground or another satellite. By receiving the signal transmitted by satellite 6800, the position of the receiver that received the signal can be measured, for example. Thus, satellite 6800 can constitute, for example, a satellite positioning system.

[0338] Alternatively, the satellite 6800 can be configured to include sensors. For example, by configuring it to include a visible light sensor, the satellite 6800 can have the function of detecting sunlight reflected off objects on the ground. Alternatively, by configuring it to include a thermal infrared sensor, the satellite 6800 can have the function of detecting thermal infrared radiation emitted from the Earth's surface. Thus, the satellite 6800 can function, for example, as an Earth observation satellite.

[0339] Figure 15(B) shows spacecraft 6900, which has a solar sail (also called a solar sail) as an example of space equipment. Spacecraft 6900 has a body 6901, a solar sail 6902, and a lithium-ion secondary battery 6905. By using the positive electrode active material particles of the present invention in the lithium-ion secondary battery, a secondary battery with high capacity, high discharge capacity, and excellent cycle characteristics can be made. When photons emitted from the sun strike the surface of the solar sail 6902, momentum is transferred to the solar sail 6902. For this reason, it is preferable that the surface of the solar sail 6902 has a thin film with high reflectivity, and more preferably that it faces the direction of the sun.

[0340] Furthermore, the Solar Sail 6902 may be designed to remain folded compactly until it leaves the Earth's atmosphere (in outer space), where it unfolds into a large sheet-like structure as shown in Figure 15(B).

[0341] FIG. 15(C) shows a spacecraft 6910 as an example of space equipment. The spacecraft 6910 includes a fuselage 6911, a solar panel 6912, and a lithium ion secondary battery 6913. By using the positive electrode active material particles of the present invention in the lithium ion secondary battery, a secondary battery with high capacity, high discharge capacity and excellent cycle characteristics can be obtained. The fuselage 6911 can have, for example, a pressurized chamber and an unpressurized chamber. The pressurized chamber may be designed to allow crew members to enter. Electric power generated by irradiating the solar panel 6912 with sunlight can charge the lithium ion secondary battery 6913.

[0342] FIG. 15(D) shows an exploration rover 6920 as an example of space equipment. The exploration rover 6920 includes a fuselage 6921 and a lithium ion secondary battery 6923. By using the positive electrode active material particles of the present invention in the lithium ion secondary battery, a secondary battery with high capacity, high discharge capacity and excellent cycle characteristics can be obtained. The exploration rover 6920 may be provided with a solar panel 6922.

[0343] The exploration rover 6920 may be designed to allow crew members to enter. The electric power generated by irradiating the solar panel 6922 with sunlight may be used to charge the lithium ion secondary battery 6923, or electric power generated by other power sources such as a fuel cell, a radioisotope thermoelectric converter, etc. may be used to charge the lithium ion secondary battery 6923.

[0344] The content of this embodiment can be appropriately combined with the content of other embodiments. [Examples]

[0345] In this example, Li x M 2-x A layered lithium-rich oxide represented by O2 (M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti and Ru, 1<x<2) is Li 1.2 Mn 0.6 Ni 0.2Positive electrode active material particles were prepared by using O2, adding fluorine and magnesium as additive elements, and heating the mixture. Their properties were then evaluated.

[0346] <Fabrication of positive electrode active material> The method for producing the positive electrode active material particles in this embodiment will be explained with reference to the manufacturing method shown in Figure 4.

[0347] First, lithium carbonate was prepared as the Li source for step S11, manganese carbonate as the Mn source, and nickel carbonate as the Ni source. These were weighed out so that Li:Mn:Ni = 1.2:0.6:0.2 (molar ratio).

[0348] Next, in step S12, a ball mill was used for wet mixing with dehydrated acetone as the solvent, while cooling. Zirconia balls with a diameter of 3 mm were used as the ball mill media, and the mixture was mixed for 2 hours. After that, the dehydrated acetone was dried in a drying oven at 55°C, and the mixed media was removed with a sieve to obtain the first mixture.

[0349] Next, as the first heating step S14, the first mixture was placed in an alumina square pod, covered, and heated using a muffle furnace while flowing dry air through it. The heating conditions were 1000°C for 10 hours. The temperature increase was 200°C / hour. The temperature decrease was 200°C / hour or less.

[0350] In the above process, the composition expected from the atomic ratio of the raw materials is Li 1.2 Mn 0.6 Ni 0.2 A composite oxide represented by O2 was obtained. This was designated as Sample 1.

[0351] Next, magnesium fluoride and lithium fluoride were prepared as the Mg source and F source for step S21. These were weighed so that LiF:MgF2 = 1:3 (molar ratio).

[0352] Next, for step S22, a ball mill was used to wet-mix the mixture using dehydrated acetone as the solvent. Zirconia balls with a diameter of 1 mm were used as the media in the ball mill, and the mixture was mixed for 20 hours. After that, the dehydrated acetone was dried in a drying oven at 55°C, and the mixed media was removed by sieving to obtain the source of added elements.

[0353] Next, as the mixing step S31, the composite oxide of sample 1, magnesium fluoride, and lithium fluoride are mixed together. 1.2 Mn 0.6 Ni 0.2 The O2:MgF2:LiF were weighed to a molar ratio of 3:0.03:0.01 and dry-mixed using a ball mill. Zirconia balls with a diameter of 1 mm were used as the media in the ball mill, and the mixture was mixed for 20 minutes. The mixed media was then removed using a sieve to obtain a second mixture.

[0354] Next, as the second heating step S33, the second mixture was placed in an alumina crucible, covered, and heated using a muffle furnace while oxygen flowed through it. The heating conditions were 900°C for 20 hours. The temperature increase was 200°C / hour. The temperature decrease was 200°C / hour or less.

[0355] The cathode active material particles produced by the above process were designated as Sample 2.

[0356] Sample 11 was prepared in the same manner as Sample 1, except that the first heating temperature was set to 900°C. Sample 12 was prepared in the same manner as Sample 2, except that the first heating temperature was set to 900°C. The preparation conditions for Sample 1, Sample 2, Sample 11, and Sample 12 are shown in Table 2.

[0357] [Table 2]

[0358] <sem> To evaluate the shape of the positive electrode active material particles, SEM images were acquired for Sample 1, Sample 2, Sample 11, and Sample 12. Figure 16(A) shows the SEM image of Sample 1, Figure 16(B) shows the SEM image of Sample 2, Figure 16(C) shows the SEM image of Sample 11, and Figure 16(D) shows the SEM image of Sample 12.

[0359] As shown in Figures 16(A) to 16(D), there was a tendency for particle size to increase after mixing the added elements and undergoing a second heating, with sample 2 having a larger particle size than sample 1, and sample 12 having a larger particle size than sample 11. However, in sample 12, where the first heating temperature was 900°C, the increase in particle size was suppressed even after mixing the added elements and undergoing a second heating.

[0360] <Charge / Discharge Curves and Charge / Discharge Cycle Characteristics> Next, to evaluate the electrochemical properties, half-cells were prepared using positive electrode active material particles from Sample 2, Sample 11, and Sample 12, and charge-discharge cycle tests were performed.

[0361] [Fabrication of the positive electrode] Samples 2, 11, and 12 were prepared as positive electrode active material particles, acetylene black (AB) was prepared as the conductive material, and polyvinylidene fluoride (PVDF) was prepared as the binder. The PVDF was prepared by dissolving it in N-methyl-2-pyrrolidone (NMP) at a weight ratio of 5%. Next, a slurry was prepared by mixing the positive electrode active material, AB, and PVDF in a weight ratio of 90:5:5, and this slurry was coated onto an aluminum positive electrode current collector. NMP was used as the solvent for the slurry. After coating the positive electrode current collector with the slurry, the solvent was evaporated.

[0362] Subsequently, to increase the density of the positive electrode active material layer on the positive electrode current collector, a press treatment was performed using a roll press machine. The press treatment conditions were a linear pressure of 210 kN / m. The upper and lower rolls of the roll press machine were both set to 120°C.

[0363] The positive electrode, after being pressed, was punched out to a diameter of 12 mm. The amount of positive electrode active material supported per unit area of ​​the positive electrode was approximately 5 mg / cm³. 2 Using this method, cathodes containing Sample 2, Sample 11, and Sample 12 were fabricated.

[0364] [Half-cell creation] Coin-shaped half-cells (also called coin cells) were fabricated using the respective positive electrodes, lithium metal foil, separator, electrolyte, coin cell positive electrode can, and coin cell negative electrode can described above. The coin-shaped half-cells were fabricated using components intended for CR2032. The size of the coin cell can be, for example, approximately 20 mm in diameter (d1 in JISC8515:2017) and approximately 3.2 mm in height (h1 in JISC8515:2017), preferably 19.5 mm to 20.5 mm in diameter and 2.8 mm to 3.5 mm in height, and more preferably 19.7 mm to 20 mm in diameter and 2.9 mm to 3.2 mm in height.

[0365] The electrolyte used was a solution prepared by dissolving 1 mol / L lithium hexafluoride phosphate (LiPF6) in a mixture of ethylene carbonate (EC) and diethyl carbonate (DEC) in a volume ratio of EC:DEC = 3:7.

[0366] Glass fiber filter paper (Whatman GF / C) was used as the separator.

[0367] A charge-discharge cycle test was performed using the half-cell prepared as described above. Charging was performed using CC (constant current), 30 mA / g, and a cutoff voltage of 4.8 V. Discharging was performed using CC, 30 mA / g, and a cutoff voltage of 2.0 V. The ambient temperature was 25°C. Unless otherwise specified, the current and charge / discharge capacity in this example are expressed per positive electrode active material particle weight.

[0368] The charge-discharge curves for the first cycle of half-cells using positive electrode active material particles of Sample 2, Sample 11, and Sample 12 are shown in Figures 17(A) to 17(C).

[0369] The initial discharge capacities were 233.4 mAh / g for sample 2 shown in Figure 17(A), 247.6 mAh / g for sample 11 shown in Figure 17(B), and 257.8 mAh / g for sample 12 shown in Figure 17(C).

[0370] Sample 2 showed increased particle size, as observed in the SEM image, which likely led to higher internal resistance and a lower initial discharge capacity compared to the other samples. Although Sample 11 had the smallest particle size, its initial discharge capacity remained below 250 mAh / g, suggesting insufficient heating temperature and / or heating time. Sample 12 exhibited an initial discharge capacity exceeding 250 mAh / g because it underwent appropriate heating temperature and / or heating time throughout the entire preparation process, and the increase in particle size was suppressed.

[0371] Figure 18 shows the charge-discharge cycle characteristics of half-cells using positive electrode active material particles for Sample 2, Sample 11, and Sample 12. After 30 cycles, the discharge capacities were 217.3 mAh / g for Sample 2, 205.9 mAh / g for Sample 11, and 220.4 mAh / g for Sample 12. In particular, Sample 12 showed a high discharge capacity of over 215 mAh / g even after 30 cycles.

[0372] As described above, lithium-rich cathode active material particles containing magnesium and fluorine as additive elements, and with high concentrations of magnesium and fluorine in the shell, exhibited good discharge capacity and cycle characteristics. In particular, sample 12, heated to 900°C in the first heating stage, showed good discharge capacity after appropriate heating temperature and / or heating time, with suppressed particle size increase. [Explanation of Symbols]

[0373] 100 Positive electrode active material particles 101 Shell 102 cores< / sem>

Claims

1. A step of mixing a lithium source and an M source (where M is one or more selected from Mn, Ni, Co, Cr, Mo, Nb, V, Fe, Ti, and Ru) to produce a first mixture, A step of synthesizing a first composite oxide by heating the first mixture at 850°C or higher and less than 950°C, A step of mixing the first composite oxide and an additive element source to produce a second mixture, The process includes the step of heating the second mixture at a temperature of 850°C or higher and 950°C or lower, The aforementioned additive element source is a fluorine source and a magnesium source, and the method for producing positive electrode active material particles.

2. In claim 1, The fluorine source is lithium fluoride. A method for producing positive electrode active material particles, wherein the magnesium source is magnesium fluoride.